Laminate and peeling method
Patent Information
- Application Number
- JP2019143265
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-08-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2039-08-02
Smart Images

Figure 0007638618000004 
Figure 0007638618000005 
Figure 0007638618000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate and a peeling method. [Background technology]
[0002] Generally, pressure-sensitive adhesives (also called pressure-sensitive adhesives; the same applies below) are in a soft solid (viscoelastic) state at temperatures around room temperature, and have the property of easily adhering to an adherend by pressure. Taking advantage of such properties, pressure-sensitive adhesives are widely used in various fields in the form of a supported adhesive sheet having an adhesive layer on a support, or in the form of a support-less adhesive sheet having no support. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2005-148638 A Summary of the Invention [Problem to be solved by the invention]
[0004] Various properties are required for adhesives depending on the application. Some of these properties are difficult to achieve at a high level, such as when one property is improved, the other property tends to decrease. One example of properties that are difficult to achieve at the same time is adhesion to an adherend and reworkability. The rework refers to, for example, peeling off an adhesive sheet from an adherend and reattaching it when a failure occurs (such as misalignment, generation of wrinkles or air bubbles, or inclusion of foreign matter) when attaching an adhesive sheet to an adherend, or when a defect is found in the adherend after the adhesive sheet is attached. Patent Document 1 discloses a method for peeling an adhesive optical film (specifically, an adhesive polarizing plate) from an optical film-attached substrate, in which the adhesive optical film is attached to the surface of a substrate (adherend) such as a glass substrate, in a state where a liquid is present at the peeling interface between the adhesive layer of the adhesive optical film and the substrate. Patent Document 1 does not discuss a method for peeling an adhesive attached to an optical film (specifically, a polarizing plate) from the optical film.
[0005] By the way, the method of using the adhesive includes a mode in which it is used in a form laminated on a substrate. In this mode, the adhesive layer and the substrate, like the adherend, desirably have both reworkability for re-attachment and adhesion during use. In some use modes, the laminate of the adhesive layer and the substrate as described above can be peeled off from the substrate after achieving its intended purpose. However, depending on the substrate material and the type of adhesive, the adhesive may not be smoothly peeled off from the substrate layer even when an aqueous liquid such as water is used. As a result of the study by the present inventors, it has become clear that a certain degree of water peelability improvement effect can be obtained by subjecting the substrate to a corona treatment or the like on the surface of the adhesive layer side in order to improve the peelability using an aqueous liquid (hereinafter, also referred to as "water peelability" for convenience), but the effect may still depend on the type of adhesive and substrate material, and it is difficult to maintain the above effect for a long period of time, so there is room for improvement in the water peelability from these substrates.
[0006] The present invention has been made in view of the above circumstances, and aims to provide a laminate having a base layer and a pressure-sensitive adhesive layer, in which the base layer and the pressure-sensitive adhesive layer are well adhered to each other, and the pressure-sensitive adhesive layer can be easily peeled off from the base layer by using an aqueous liquid such as water. Another aim of the present invention is to provide a method for peeling the pressure-sensitive adhesive layer from the base layer. [Means for solving the problem]
[0007] According to this specification, a laminate is provided having a base layer and a pressure-sensitive adhesive layer releasably laminated to the base layer. The pressure-sensitive adhesive layer includes an A layer constituting a surface on the side of the base layer. A hydrophilic layer is formed on the surface of the base layer on the side of the pressure-sensitive adhesive layer. The hydrophilic layer is an inorganic material-containing layer. The peel strength N0 of the pressure-sensitive adhesive layer relative to the base layer is 2.0 N / 10 mm or more. The laminate is then subjected to a test in which 20 μL of distilled water is supplied between the base layer and the pressure-sensitive adhesive layer, the distilled water is allowed to penetrate into one end of the interface between the pressure-sensitive adhesive layer and the base layer, and then the water peel strength reduction rate is calculated by the following formula: (1-(N2 / N0))×100; from the water peel strength N2 [N / 10 mm] measured at a test temperature of 23° C., a tensile speed of 300 mm / min, and a peel angle of 180° using a tensile tester, and the peel strength N0 [N / 10 mm], and is 40% or more. According to the above configuration, the adhesive layer of the laminate adheres to the base layer with a peel strength equal to or greater than a predetermined value, while a specific hydrophilic layer is present on the adhesive layer side surface of the base layer. Therefore, the adhesive layer can be easily peeled off by applying an aqueous liquid such as water to the surface of the base layer and allowing it to penetrate to the interface between the surface of the base layer and the surface of the adhesive layer.
[0008] In some preferred embodiments of the laminate, the peel strength N0 is 3.0 N / 10 mm or more. This configuration allows the pressure-sensitive adhesive layer of the laminate to be more stably adhered to the base layer. Also, the laminate can be more strongly adhered to the adherend.
[0009] In some preferred embodiments, the laminate has a peel strength reduction rate after water immersion of 30% or less, calculated from the peel strength N1 [N / 10 mm] after water immersion, which is measured after the laminate is immersed in water for 30 minutes, then removed from the water and the adhering water is wiped off, and the peel strength N0 [N / 10 mm] according to the following formula: (1-(N1 / N0)) x 100. A laminate containing a pressure-sensitive adhesive that satisfies the above peel strength reduction rate after water immersion (30% or less) has excellent water resistance reliability.
[0010] In some preferred embodiments, the layer A is a layer formed from a photocurable or solvent-based pressure-sensitive adhesive composition. In a configuration including a layer A formed from a photocurable or solvent-based pressure-sensitive adhesive composition, the effect of the technology disclosed herein (the effect of improving water peelability by forming a hydrophilic layer) is preferably exhibited. In addition, when the laminate disclosed herein is used for optical purposes, the photocurable or solvent-based pressure-sensitive adhesive is more likely to exhibit excellent optical properties than the water-dispersible type.
[0011] In some preferred embodiments, the layer A contains a hydrophilic agent. The layer A containing a hydrophilic agent makes it easier to obtain a PSA that satisfies both normal state (standard) peel strength and water releasability, and further makes it easier to obtain a PSA that has a suppressed rate of loss in peel strength after immersion in water.
[0012] In some preferred embodiments, the inorganic material is an inorganic oxide. By using an inorganic oxide as a material for the hydrophilic layer on the surface of the base layer on the side of the pressure-sensitive adhesive layer, the water contact angle of the surface is effectively reduced, and excellent water peelability is easily obtained. Silicon oxide is particularly preferably used as the inorganic oxide.
[0013] In some embodiments, the thickness of the hydrophilic layer is less than 5000 nm. By making the hydrophilic layer as thin as this, it is possible to improve the water peelability without impairing the function of the base layer.
[0014] In some preferred embodiments, the substrate layer is an optical member. The laminate disclosed herein can be preferably used in the form of an optical member with adhesive suitable for optical applications. The optical laminate (optical member with adhesive) has a substrate layer and an adhesive layer as its constituent elements bonded reliably, and has excellent reworkability using water peeling, so that re-attachment is easy, and after the intended use of the laminate is achieved, the two can be easily separated using the water peeling property.
[0015] Also, according to this specification, a method for peeling the adhesive layer from a base layer of a laminate having a base layer and an adhesive layer is provided. This method includes a water peeling step of peeling the adhesive layer from the base layer while advancing the intrusion of the aqueous liquid into the interface in accordance with the movement of the peel front, in a state where an aqueous liquid is present at the interface between the base layer and the adhesive layer at the peel front of the adhesive layer from the base layer. Here, the peel front refers to a location where the adhesive layer starts to separate from the base layer when the peeling of the adhesive layer from the base layer progresses. In addition, the adhesive layer includes a layer A constituting the base layer side surface. Furthermore, the adhesive layer side surface of the base layer is subjected to a hydrophilic treatment. According to the water peeling step, since the adhesive layer side surface of the base layer is subjected to a hydrophilic treatment, the aqueous liquid can be effectively used to peel the adhesive layer from the base layer. In some preferred embodiments, the hydrophilic treatment is the formation of a hydrophilic layer on the adhesive layer side surface of the base layer. In a particularly preferred embodiment, the hydrophilic layer is an inorganic material-containing layer. In some embodiments, at least layer A constituting the surface of the pressure-sensitive adhesive layer on the side of the base layer is preferably composed of a pressure-sensitive adhesive containing a hydrophilic agent. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a cross-sectional view that illustrates a schematic configuration of the laminate. [Diagram 2] FIG. 2 is a cross-sectional view that illustrates a schematic configuration of another laminate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] A preferred embodiment of the present invention will be described below. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention can be understood by a person skilled in the art based on the teachings on carrying out the invention described in this specification and the common general knowledge at the time of filing. The present invention can be carried out based on the contents disclosed in this specification and the common general knowledge in the field. In addition, in the following drawings, components and parts having the same function may be described by using the same reference numerals, and duplicated descriptions may be omitted or simplified. In addition, the embodiments described in the drawings are schematic in order to clearly explain the present invention, and do not necessarily accurately represent the size or scale of the product actually provided.
[0018] In this specification, the term "acrylic polymer" refers to a polymer derived from a monomer component containing more than 50% by weight of an acrylic monomer. The acrylic monomer refers to a monomer derived from a monomer having at least one (meth)acryloyl group in one molecule. In addition, in this specification, "(meth)acryloyl" refers to acryloyl and methacryloyl collectively. Similarly, "(meth)acrylate" refers to acrylate and methacrylate, and "(meth)acrylic" refers to acrylic and methacrylic collectively. The acrylic polymer may be an acrylic polymer. The acrylic polymer may be, for example, an acrylic polymer contained as a base polymer (main constituent polymer) in a water-dispersed or solvent-based pressure-sensitive adhesive. In this case, the "monomer component constituting the acrylic polymer" in this specification can be rephrased as "monomer component constituting the acrylic polymer". In addition, in this specification, the content of an additive component expressed in terms of a relative amount to the "monomer component constituting the polymer" or the "monomer component constituting the acrylic polymer" can be rephrased as a relative amount to the "acrylic polymer."
[0019] <Example of laminate configuration> An example of the structure of the laminate disclosed herein is shown in FIG. 1. The laminate 1 is configured as a single-sided adhesive sheet including an adhesive layer 10 and a base layer 20 laminated on one surface 10A of the adhesive layer 10. The base layer 20 has a laminated structure of a main layer 22 and a hydrophilic layer 24, specifically, the main layer 22 and the hydrophilic layer 24 constituting the surface 20B on the adhesive layer 10 side. The adhesive layer 10 is releasably adhered to the adhesive layer side surface 20B of the base layer 20. The adhesive layer 10 is laminated in a state of direct contact with the hydrophilic layer 24 of the base layer 20. In the example shown in FIG. 1, the adhesive layer 10 has a single layer structure. That is, the entire adhesive layer 10 is constituted by Layer A constituting one surface (base layer side surface) 10A of the adhesive layer 10. The laminate 1 before use (before attachment to an adherend) may be in the form of a release-liner laminate 50 in which the other surface (adhesive surface) 10B of the adhesive layer 10 is protected by a release liner 30 having at least the adhesive layer side as a releasable surface (release surface), as shown in Fig. 1. Alternatively, the back surface 20A of the base layer 20 (the surface opposite to the adhesive layer side surface 20B; it may also be the back surface of the laminate 1) is the release surface, and the adhesive surface 10B may be protected by being wound or laminated so that the adhesive surface 10B abuts against the back surface 20A.
[0020] Another structural example of the laminate disclosed herein is shown in FIG. 2. The laminate 2 is configured as a single-sided adhesive sheet including an adhesive layer 110 and a base layer 20 laminated on one surface (base layer side surface) 110A of the adhesive layer 110. The base layer 20 has a laminated structure of a main layer 22 and a hydrophilic layer 24, specifically, the main layer 22 and the hydrophilic layer 24 constituting the surface 20B on the adhesive layer 10 side. The adhesive layer 110 has a two-layer structure consisting of an A layer 112 constituting one surface (base layer side surface) 110A and a B layer 114 laminated on the back side of the A layer 112. The A layer 112 of the adhesive layer 110 is releasably adhered to the adhesive layer side surface 20B of the base layer 20. Specifically, the A layer 112 is laminated in a state of direct contact with the hydrophilic layer 24 of the base layer 20. The laminate 2 before use (before attachment to an adherend) may be in the form of a laminate with a release liner, in which the other surface (adhesive surface) 110B is protected by a release liner (not shown), similar to the laminate 1 shown in Fig. 1. Alternatively, the back surface 20A of the base layer 20 (which may also be the back surface of the laminate 2) is the release surface, and the adhesive surface 110B may be protected by being wound or laminated so that the adhesive surface 110B abuts against the back surface 20A.
[0021] The release liner is not particularly limited, and may be, for example, a release liner in which the surface of a liner substrate such as a resin film or paper is release-treated, or a release liner made of a low-adhesion material such as a fluorine-based polymer (polytetrafluoroethylene, etc.) or a polyolefin-based resin (polyethylene, polypropylene, etc.). For the release treatment, for example, a silicone-based or long-chain alkyl-based release treating agent may be used. In some embodiments, a release-treated resin film may be preferably used as the release liner.
[0022] <Characteristics of laminate> (peel strength N0) In the laminate disclosed herein, the peel strength N0 of the adhesive layer to the base layer is 2.0 N / 10 mm or more. Here, the peel strength N0 is a peel strength measured under the conditions of a temperature of 23° C., a tensile speed of 300 mm / min, and a peel angle of 180°. In other words, the adhesive layer is adhered to the base layer with a peel strength N0 of a predetermined value or more. This allows the adhesive layer of the laminate to be stably adhered to the base layer, and prevents the occurrence of problems such as the adhesive layer unintentionally peeling off from the base layer during use. A laminate having the above peel strength can also exhibit good adhesion to an adherend. In some embodiments, the peel strength N0 may be, for example, 2.5N / 10mm or more, 3.0N / 10mm or more, 3.5N / 10mm or more, 4.0N / 10mm or more, 4.5N / 10mm or more, or 5.0N / 10mm or more, from the viewpoint of the adhesion between the pressure-sensitive adhesive layer and the base material layer and the adhesion to the adherend. In some other embodiments, the peel strength N0 may be, for example, 6.0N / 10mm or more, 7.0N / 10mm or more, 8.0N / 10mm or more, 9.0N / 10mm or more, 10.0N / 10mm or more, or 11.0N / 10mm or more. The upper limit of the peel strength N0 is not particularly limited, and may be, for example, 30N / 10mm or less. The peel strength N0 may be 20 N / 10 mm or less, or 15 N / 10 mm or less (e.g., 12 N / 10 mm or less). In some embodiments, the peel strength N0 may be less than 10 N / 10 mm, or less than 8 N / 10 mm. The peel strength N0 is specifically measured by the method described in the Examples below.
[0023] (Water peeling force N2) The laminate disclosed herein may have a water peeling force N2 [N / 10 mm] measured at a test temperature of 23° C. using a tensile tester at a tensile speed of 300 mm / min and a peeling angle of 180°, in accordance with JIS Z0237:2009, 10.4.1, Method 1: 180° peel adhesion to test plate, after supplying 20 μL of distilled water between the base layer and the adhesive layer, and then allowing the distilled water to penetrate into one end of the interface between the adhesive layer and the base layer, and the water peeling force N2 [N / 10 mm] measured at a test temperature of 23° C. using a tensile tester at a tensile speed of 300 mm / min and a peeling angle of 180° is limited to a predetermined value or less. With a laminate with a limited water peeling force N2, the adhesive layer can be easily peeled off by applying an aqueous liquid such as water to the surface of the base layer and allowing it to penetrate into the interface between the surface of the base layer and the surface of the adhesive layer. The water peeling force N2 is preferably 60% or less of the peel strength N0 (N2≦0.6N0). That is, the water peeling force N2 [N / 10 mm] is preferably 40% or more in the below-described formula: water peeling force reduction rate [%] = (1-(N2 / N0)) x 100; that is, (1-(N2 / N0)) x 100 ≧ 40 [%];. This formula means the following formula: N2 ≦ 0.6N0;. Although not particularly limited, the water peeling force N2 may be, for example, 10 N / 10 mm or less, 3.5 N / 10 mm or less, 2.5 N / 10 mm or less, 1.6 N / 10 mm or less, 1.2 N / 10 mm or less, or 1.0 N / 10 mm or less. A laminate with a low water peeling force N2 can reduce the load applied to the base layer when peeling off the pressure-sensitive adhesive layer. This is particularly significant in that, for example, in an embodiment in which the base layer is an optical member, when the pressure-sensitive adhesive layer is peeled off from the optical member, the surface of the optical member is not affected by peeling.The above laminate can also be preferably implemented in an embodiment in which the water peeling force N2 is, for example, 0.75N / 10mm or less, or 0.50N / 10mm or less, or 0.25N / 10mm or less, or 0.15N / 10mm or less.The lower limit of the water peeling force N2 is not particularly limited, and may be substantially 0N / 10mm or more than 0N / 10mm. In addition, from the viewpoint of reworkability, it is preferable that the adhesive layer can be peeled off from the base layer without leaving any adhesive on the base layer in the measurement of water peeling force N2. That is, it is preferable that the adhesive layer has excellent non-adhesive residue property in peeling off from the base layer. The presence or absence of adhesive remaining on the base layer can be grasped, for example, by visually observing the base layer after peeling off the adhesive layer. The water peeling force N2 is specifically measured by the method described in the Examples below.
[0024] (Water peeling force reduction rate) The laminate disclosed herein has a water peel strength reduction rate of 40% or more. The laminate showing the water peel strength reduction rate can easily peel the adhesive layer from the base layer by using an aqueous liquid such as water. For example, a small amount of aqueous liquid is supplied between the base layer and the adhesive layer of the laminate, and the aqueous liquid is allowed to enter the interface between the base layer and the adhesive layer from one end of the laminate to trigger peeling, thereby greatly reducing the peel strength of the adhesive layer from the base layer. By utilizing this property, high adhesion and good peelability during normal use can be achieved at the same time. In some embodiments, the water peel strength reduction rate may be, for example, 50% or more, 65% or more, 75% or more, 85% or more, 90% or more, 95% or more, or 97% or more. The water peel strength reduction rate is, in principle, 100% or less, and typically less than 100%. The water peel strength reduction rate is calculated by the formula: Water peeling force reduction rate [%] = (1-(N2 / N0)) x 100 In the technology disclosed herein, the above-mentioned water peel strength reduction rate is realized by selecting the formation of a hydrophilic layer, the materials constituting the hydrophilic layer, the type and composition of the adhesive, and the like.
[0025] The ratio (N2 / N0) of the water peeling force N2 [N / 10 mm] to the peel strength N0 [N / 10 mm] may be, for example, 1 / 2.5 or less, 1 / 5 or less, or 1 / 10 or less. A smaller ratio (N2 / N0) means that the water peeling force N2 is more significantly reduced relative to the peel strength N0. The laminate disclosed herein may be preferably implemented in an embodiment in which the ratio (N2 / N0) is 1 / 15 or less, 1 / 25 or less, or 1 / 35 or less. The lower limit of the ratio (N2 / N0) is not particularly limited, and may be, for example, 1 / 200 or more, 1 / 150 or more, or 1 / 100 or more.
[0026] (Removal force reduction rate after water immersion) The laminate disclosed herein can be easily peeled off using an aqueous liquid such as water as described above, and the laminate can be immersed in water for 30 minutes, then removed from the water and wiped off the adhering water, and thereafter the peel strength after water immersion N1 [N / 10 mm] measured under the same conditions as those for measuring the peel strength N0 can be expressed by the formula: Peel strength reduction rate after water immersion [%] = (1-(N1 / N0)) x 100 In the above formula, it is preferable that the peel strength reduction rate after immersion in water is 30% or less. (1-(N1 / N0)) x 100 ≤ 30[%] It is preferable to satisfy the following formula: N1≧0.7N0. A laminate containing a pressure-sensitive adhesive that satisfies the above-mentioned water-immersion peel strength reduction rate (30% or less) is excellent in water resistance reliability. From the viewpoint of obtaining higher water resistance reliability, the water-immersion peel strength reduction rate is, for example, preferably 20% or less, more preferably 10% or less, and may be 7% or less. The lower limit of the water-immersion peel strength reduction rate is typically 0% or more. The above-mentioned laminate can be preferably implemented in an embodiment in which the difference between the water-immersion peel strength reduction rate [%] and the water-immersion peel strength reduction rate [%] is, for example, 45% or more, or 55% or more, or 70% or more, or 80% or more, or 90% or more. The water-immersion peel strength N1 for calculating the water-immersion peel strength reduction rate is measured by the method described in the Examples below.
[0027] In some embodiments, the haze value of the laminate is suitably about 10% or less, and may be about 5% or less (e.g., about 3% or less). The haze value is preferably 1.0% or less. Such a highly transparent laminate is suitable for optical applications requiring high light transmittance. The haze value of the laminate may be less than 1.0%, may be less than 0.7%, or may be 0.5% or less (e.g., 0 to 0.5%). The above haze value range for the laminate may also be applied to the haze values of the pressure-sensitive adhesive layer and the base layer in the technology disclosed herein.
[0028] Here, the "haze value" refers to the ratio of diffuse transmitted light to the total transmitted light when a measurement target is irradiated with visible light. It is also called the cloudiness value. The haze value can be expressed by the following formula. Th[%]=Td / Tt×100 In the above formula, Th is the haze value [%], Td is the scattered light transmittance, and Tt is the total light transmittance. The haze value can be measured using a haze meter (for example, "MR-100" manufactured by Murakami Color Research Laboratory). The haze value can be adjusted, for example, by selecting the composition and thickness of the adhesive layer, the material and thickness of the base layer, etc.
[0029] In the laminate, the adhesive constituting the A layer arranged on the surface side of the adhesive layer on the substrate layer side is preferably water-insoluble. The water-insoluble A layer makes it easy to obtain a laminate having a high peel strength N1 after immersion in water and a low peel strength reduction rate after immersion in water. The water-insoluble A layer is also preferable from the viewpoint of preventing the phenomenon that the adhesive remains on the substrate layer during peeling using an aqueous liquid such as water. In addition, the water-insoluble A layer can be advantageous from the viewpoint of preventing the phenomenon that the transparency of the laminate decreases due to water immersion or moisture in the environment. This can be an advantageous feature in an optical laminate in which the substrate layer is an optical member.
[0030] The adhesive constituting the A layer is preferably non-water-swellable. The non-water-swellable A layer is likely to produce a laminate with high peel strength N1 after immersion in water and low peel strength reduction rate after immersion in water. In addition, in peeling using an aqueous liquid such as water, a small amount of aqueous liquid can be effectively used to exhibit good peelability. The fact that the A layer is non-water-swellable is also preferable from the viewpoint of preventing the phenomenon in which the adhesive remains on the base layer in peeling using an aqueous liquid. In addition, the fact that the A layer is non-water-swellable can be advantageous from the viewpoint of preventing the phenomenon in which the transparency of the laminate decreases due to immersion in water or moisture in the environment. This can be an advantageous feature in an optical laminate in which the base layer is an optical member.
[0031] In this specification, a pressure-sensitive adhesive being water-insoluble means that the gel fraction measured by the following method is 75% or more, and a pressure-sensitive adhesive being non-water-swellable means that the swelling degree measured by the following method is 2 or less. That is, about 0.5 g of the adhesive to be measured is weighed out, and the weight is designated as W1. The adhesive is immersed in 500 ml of distilled water at room temperature (approximately 23°C) for 48 hours, then filtered through a nylon mesh, and the weight of the adhesive containing water, W2, is measured. The adhesive is then dried at 130°C for 5 hours, and the weight of the non-volatile content, W3, is measured. The gel fraction and swelling degree are calculated by the following formulas. Gel fraction [%] = (W3 / W1) × 100 Swelling degree = W2 / W1
[0032] In some embodiments, the gel fraction of the A layer may be, for example, 80% or more, 90% or more, 95% or more, or 98% or more. The gel fraction of the A layer is, in principle, 100% or less. In some embodiments, the swelling degree of the A layer may be, for example, 1.7 or less, 1.5 or less, or 1.2 or less. The swelling degree of the A layer is, for example, 1.0 or more, typically more than 1.0.
[0033] In a laminate in which the pressure-sensitive adhesive layer includes a layer A and a layer B arranged on the back side of the layer A, the gel fraction of the layer B is not particularly limited. In some embodiments, the gel fraction of the layer B is preferably equal to or greater than the gel fraction of the layer A, and may be higher than the gel fraction of the layer A. The gel fraction of the layer B may be, for example, 90% or more, 95% or more, 98% or more, or 99% or more. The gel fraction of the layer B is, in principle, 100% or less. The gel fraction of the entire pressure-sensitive adhesive layer may be, for example, 85% or more, 90% or more, 95% or more, 98% or more, or 99% or more. In a pressure-sensitive adhesive layer consisting of only a layer A, the gel fraction of the entire pressure-sensitive adhesive layer means the gel fraction of the layer A.
[0034] In a laminate in which the pressure-sensitive adhesive layer includes an A layer and a B layer disposed on the back side of the A layer, the swelling degree of the B layer is not particularly limited. In some embodiments, the swelling degree of the B layer is preferably equal to or less than the swelling degree of the A layer, and may be lower than the swelling degree of the A layer. The swelling degree of the B layer may be, for example, 1.5 or less, 1.3 or less, or 1.1 or less. The swelling degree of the B layer is, for example, 1.0 or more, typically more than 1.0. The swelling degree of the entire pressure-sensitive adhesive layer may be, for example, 1.6 or less, 1.4 or less, 1.2 or less, or 1.1 or less. In a pressure-sensitive adhesive layer consisting of only an A layer, the swelling degree of the entire pressure-sensitive adhesive layer means the swelling degree of the A layer.
[0035] The gel fraction and swelling degree of the pressure-sensitive adhesive in water can be adjusted by appropriately adopting methods that would be common to those skilled in the art at the time of filing this application, such as the composition of the monomer components, the weight-average molecular weight of the polymer, and the use of a crosslinking agent or a polyfunctional monomer.
[0036] <Base material layer> (hydrophilic layer) The substrate layer constituting the laminate disclosed herein has a hydrophilic layer formed on the surface on the side of the adhesive layer. In other words, the substrate layer has a hydrophilic layer as a layer constituting the surface on the side of the adhesive layer (the outermost layer of the substrate layer). Here, the hydrophilic layer is defined as a layer having a hydrophilic surface, and for example, the surface of the hydrophilic layer before lamination of the adhesive layer (also the surface on the side of the adhesive layer of the substrate layer. The same applies hereinafter unless otherwise specified) may be a surface exhibiting hydrophilicity such that the contact angle with distilled water (hereinafter also referred to as "water contact angle") is, for example, 60 degrees or less, preferably 50 degrees or less. By providing a hydrophilic layer on the surface on the side of the adhesive layer of the substrate layer, good water peelability can be obtained regardless of the substrate material, the type of adhesive laminated thereon, etc.
[0037] In some embodiments, the water contact angle of the hydrophilic layer surface may be, for example, 45 degrees or less, 40 degrees or less, 35 degrees or less, or 30 degrees or less. When the water contact angle of the hydrophilic layer surface is small, water tends to spread easily along the surface, and the water peelability of the pressure-sensitive adhesive layer from the base layer tends to improve. This is preferable from the viewpoint of removability of the pressure-sensitive adhesive layer from the base layer and improvement of reworkability. In some preferred embodiments, the water contact angle of the hydrophilic layer surface is suitably less than 25 degrees, and may be less than 20 degrees, 15 degrees or less, or less than 10 degrees. The lower limit of the water contact angle is 0 degrees in principle. In some embodiments, the water contact angle may be more than 0 degrees, 1 degree or more, 3 degrees or more, or 5 degrees or more. According to the technology disclosed herein, better water peelability can be achieved by selecting the hydrophilic layer material and the adhesive type, so in some embodiments, the water contact angle of the hydrophilic layer surface may be 8 degrees or more, 12 degrees or more, 16 degrees or more, or 20 degrees or more (e.g., 24 degrees or more). The water contact angle of the hydrophilic layer surface can be set by selecting the material constituting the hydrophilic layer, the thickness of the hydrophilic layer, additional surface treatment, etc. The water contact angle of the hydrophilic layer surface (the adhesive layer side surface of the substrate layer) can be measured by the method described in the Examples below.
[0038] The technology disclosed herein can form a hydrophilic layer on the adhesive layer side surface of the base layer to reduce the water contact angle of the adhesive layer side surface and obtain improved water peelability. Therefore, the water contact angle WCA1 of the hydrophilic layer surface is typically smaller than the water contact angle WCA2 of the surface of the main layer of the base layer (base layer alone without hydrophilic layer) described below. The WCA1 is preferably less than 70% of the WCA2, more preferably less than 50%, even more preferably less than 30%, and particularly preferably less than 20%.
[0039] From the viewpoint of water peelability, the hydrophilic layer surface is preferably formed smoothly. For example, the arithmetic mean roughness Ra of the hydrophilic layer surface is less than 10 μm. With a hydrophilic layer surface with such suppressed unevenness, it is easy to achieve the desired water peelability. The arithmetic mean roughness Ra is preferably less than 5 μm, more preferably less than 3 μm (specifically less than 1.0 μm). From the viewpoint of maintaining water peelability for a long period of time, the arithmetic mean roughness Ra of the hydrophilic surface is preferably even smaller. For example, the arithmetic mean roughness Ra is preferably less than 100 nm, more preferably less than 10 nm, and even more preferably less than 3 nm (specifically less than 1.0 nm). The surface smoothness of the hydrophilic layer can be adjusted by the selection of the hydrophilic layer material, the formation conditions, the thickness, etc. In this specification, the arithmetic average roughness can be measured using a general surface roughness measuring device (for example, a non-contact three-dimensional surface profile measuring device manufactured by Veeco, model "Wyko NT-3300", or an atomic force microscope manufactured by Hitachi High-Technologies Corporation, model "AFM5500M").
[0040] As the material of the hydrophilic layer, an inorganic material is used. By including an inorganic material in the hydrophilic layer, good water peelability is easily obtained. As the inorganic material, a material capable of forming a hydrophilic surface is used from among various metal materials including simple substances and alloys of transition metal elements and semimetal elements, and inorganic compounds such as inorganic oxides. The above inorganic materials can be used alone or in combination of two or more. Suitable examples of the inorganic material include oxides (inorganic oxides, typically metal oxides) such as titanium oxide, zinc oxide, magnesium oxide, aluminum oxide, silicon oxide, cerium oxide, chromium oxide, zirconium oxide, manganese oxide, zinc oxide, iron oxide, tin oxide, and niobium oxide. Among them, inorganic oxides such as silicon oxide are used as a preferred inorganic material. In addition to the inorganic material, the hydrophilic layer may or may not include various organic materials including organic polymer compounds that can be used as coating agents or binders.
[0041] The amount of inorganic material (e.g., inorganic oxide such as silicon oxide) in the hydrophilic layer can be an appropriate amount that can obtain a desired hydrophilic surface, and is not limited to a specific range. For example, the content of inorganic material in the hydrophilic layer can be about 30% by weight or more, and is suitably about 50% by weight or more (e.g., more than 50% by weight), and may be about 70% by weight or more. In some preferred embodiments, the content of inorganic material in the hydrophilic layer is about 90 to 100% by weight (e.g., about 95% by weight or more).
[0042] In some preferred embodiments, the inorganic material is silicon oxide (typically SiO X Inorganic oxides such as silicon oxide represented by SiO2 and silicon dioxide represented by SiO2 are used. The proportion of the inorganic oxide (typically silicon oxide) in the inorganic material can be an appropriate amount that can obtain a desired hydrophilic surface, and is not limited to a specific range, and can be, for example, about 30% by weight or more, suitably about 50% by weight or more (e.g., more than 50% by weight), and may be about 70% by weight or more. In some preferred embodiments, the proportion of the inorganic oxide (typically silicon oxide) in the inorganic material is about 90 to 100% by weight (e.g., about 95% by weight or more).
[0043] The method of forming the hydrophilic layer is not particularly limited, and the layer can be formed by an appropriate method depending on the desired thickness. For example, an inorganic material formed in a layer shape using a known film forming method such as a vacuum deposition method, a sputtering method, or a plating method can be used as the hydrophilic layer. When an inorganic compound is used as the inorganic material, various deposition methods can be used, for example, physical vapor deposition (PVD) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition (CVD) such as atomic layer deposition can be adopted. The formation of a coating layer containing an inorganic polymer such as polysiloxane can be carried out by appropriately selecting from known coating agents that can provide a surface showing a desired water contact angle and using the agent in a conventional manner.
[0044] The thickness of the hydrophilic layer is not particularly limited. From the viewpoint of not impairing the function of the substrate layer body (main layer of the substrate layer), the thickness of the hydrophilic layer is specifically about 5 μm or less (for example, less than 5000 nm), and may be about 2 μm or less (for example, less than 2000 nm). In some preferred embodiments, the thickness of the hydrophilic layer is less than 1000 nm, more preferably less than 500 nm, even more preferably less than 100 nm, particularly preferably less than 50 nm, and may be about 30 nm or less, about 20 nm or less, or about 15 nm or less (for example, less than 10 nm). By making the hydrophilic layer thin, it is possible to improve the water peelability without impairing the function of the substrate layer. Making the hydrophilic layer thin is also advantageous from the viewpoint of optical properties. In addition, the thickness of the hydrophilic layer is suitable to be 1 nm or more (for example, 3 nm or more), and from the viewpoint of increasing the hydrophilicity of the surface and improving the water peelability, it may be about 5 nm or more, or may be about 10 nm or more (for example, 15 nm or more). For a thin hydrophilic layer (eg, on the nano-order), the thickness can be measured by the method described in the Examples below.
[0045] (base material main layer) The main layer of the substrate layer disclosed herein (also referred to as "substrate main layer", or simply referred to as "substrate layer" for convenience. The same applies hereinafter unless otherwise specified) is not particularly limited and can be appropriately selected according to the purpose of use, the mode of use, and the like. The technology disclosed herein can form a hydrophilic layer on the adhesive layer side surface of the substrate layer to reduce the water contact angle of the adhesive layer side surface and obtain improved water peelability. Therefore, the water contact angle of the surface of the substrate layer alone (main layer) without a hydrophilic layer is typically larger than the water contact angle of the hydrophilic layer surface. The water contact angle of the substrate main layer surface can be, for example, higher than 10 degrees, more than 30 degrees, or more than 50 degrees. The water contact angle of the substrate main layer surface can be 60 degrees or more, 70 degrees or more, or 80 degrees or more (for example, 85 degrees or more) from the viewpoint of better exerting the effect of forming the hydrophilic layer. The upper limit of the water contact angle of the substrate main layer surface is not particularly limited, and can be, for example, less than 115 degrees, less than 105 degrees, or less than 95 degrees. The substrate main layer disclosed herein may have a water contact angle in the above range on its hydrophilic layer side surface. The water contact angle on the back surface of the substrate layer may be in the same range as the water contact angle of the substrate main layer. The water contact angle of the substrate main layer surface can be measured by the method described in the Examples below.
[0046] Non-limiting examples of the material of the substrate main layer include various resin films such as polyolefin film, polyester film, polyvinyl chloride film, etc.; foam sheets made of foams such as polyurethane foam, polyethylene foam, polychloroprene foam, etc.; woven and nonwoven fabrics made by single or mixed spinning of various fibrous materials (natural fibers such as hemp and cotton, synthetic fibers such as polyester and vinylon, semi-synthetic fibers such as acetate, etc.); papers such as Japanese paper, fine paper, craft paper, crepe paper, etc.; metal foils such as aluminum foil, copper foil, stainless steel (SUS), etc.; and the like. A layered body having a composite structure of these may also be used. Examples of the substrate main layer having such a composite structure include, for example, a laminated substrate (multilayer structure substrate) having a structure in which a metal foil and the above-mentioned resin film are laminated, and a resin sheet reinforced with inorganic fibers such as glass cloth.
[0047] As the material of the substrate main layer, various films (hereinafter, also referred to as substrate film) can be preferably used. The substrate film may be a porous film such as a foam film or a nonwoven sheet, or may be a nonporous film, or may be a film having a structure in which a porous layer and a nonporous layer are laminated. In some embodiments, the substrate film may preferably be one containing a resin film that can independently maintain its shape (self-supporting or independent) as a base film. Here, the term "resin film" means a resin film having a nonporous structure and typically containing substantially no air bubbles (voidless). Therefore, the resin film is a concept that is distinguished from foam films and nonwoven fabrics. The resin film may be a single-layer structure, or may be a multi-layer structure of two or more layers (for example, a three-layer structure).
[0048] Examples of resin materials that can be used to form the resin film include polyesters such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT); polyolefins such as polypropylene and ethylene-propylene copolymers; polycycloolefins derived from monomers having an aliphatic ring structure such as a norbornene structure; polyamides (PA) such as nylon 6, nylon 66, and partially aromatic polyamides; polyimides (PI) such as transparent polyimide (CPI), polyamideimide (PAI); polyether ether ketone (PEEK); polyethersulfone (PES); polyphenylene sulfide (PPS); polycarbonate (PC); polyurethane (PU); ethylene-vinyl acetate copolymer (EVA); polyvinyl alcohol (PVA); polystyrene; ABS resin; polyvinyl chloride; polyvinylidene chloride; fluororesins such as polytetrafluoroethylene (PTFE); acrylic resins such as polymethyl methacrylate; cellulose-based polymers such as diacetyl cellulose and triacetyl cellulose (TAC); vinyl butyral-based polymers; arylate-based polymers; polyoxymethylene-based polymers; and epoxy-based polymers. The substrate main layer disclosed herein may have a surface made of the above resin material. The resin film that can be used as the substrate main layer may be formed using a resin material containing one of the above resins alone, or may be formed using a resin material in which two or more types are blended. The resin film may be a composite resin film in which a resin layer containing one or more resin materials and a resin layer containing one or more resin materials of the same or different type as the resin layer are laminated. The resin film may be unstretched or stretched (for example, uniaxially or biaxially stretched).
[0049] Suitable examples of resin materials constituting the resin film include polyester-based resin, PPS resin, polyolefin-based resin, and polyimide resin. Here, polyester-based resin refers to a resin containing polyester at a ratio of more than 50% by weight. Similarly, PPS resin refers to a resin containing PPS at a ratio of more than 50% by weight, polyolefin-based resin refers to a resin containing polyolefin at a ratio of more than 50% by weight, and polyimide resin refers to a resin containing polyimide at a ratio of more than 50% by weight.
[0050] As the polyester-based resin, typically, a polyester-based resin containing, as a main component, a polyester obtained by polycondensation of a dicarboxylic acid and a diol is used. Specific examples of the polyester-based resin include polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polybutylene naphthalate, etc.
[0051] As the polyolefin resin, one type of polyolefin can be used alone, or two or more types of polyolefins can be used in combination. The polyolefin can be, for example, a homopolymer of an α-olefin, a copolymer of two or more types of α-olefins, or a copolymer of one or more types of α-olefins and other vinyl monomers. Specific examples include polyethylene (PE), polypropylene (PP), poly-1-butene, poly-4-methyl-1-pentene, ethylene-propylene copolymers such as ethylene-propylene rubber (EPR), ethylene-propylene-butene copolymers, ethylene-butene copolymers, ethylene-vinyl alcohol copolymers, and ethylene-ethyl acrylate copolymers. Both low density (LD) polyolefins and high density (HD) polyolefins can be used. Examples of polyolefin resin films include non-oriented polypropylene (CPP) film, biaxially oriented polypropylene (OPP) film, low-density polyethylene (LDPE) film, linear low-density polyethylene (LLDPE) film, medium-density polyethylene (MDPE) film, high-density polyethylene (HDPE) film, polyethylene (PE) film made by blending two or more types of polyethylene (PE), and PP / PE blend film made by blending polypropylene (PP) and polyethylene (PE).
[0052] Specific examples of resin films that can be preferably used as the substrate main layer include PET film, PEN film, PPS film, PEEK film, CPI film, CPP film, OPP film, and TAC film. Preferred examples from the viewpoint of strength include PET film, PEN film, PPS film, PEEK film, and CPI film. Preferred examples from the viewpoint of availability, dimensional stability, optical properties, etc. include PET film, CPI film, and TAC film.
[0053] The resin film may contain known additives such as light stabilizers, antioxidants, antistatic agents, colorants (dyes, pigments, etc.), fillers, slip agents, antiblocking agents, etc., as necessary. The amount of additives to be added is not particularly limited, and can be appropriately set depending on the application, etc.
[0054] The method for producing the resin film is not particularly limited, and may be any of the conventionally known general resin film forming methods, such as extrusion molding, inflation molding, T-die casting, and calendar roll molding.
[0055] The substrate main layer may be substantially composed of such a resin film. Alternatively, the substrate main layer may include an auxiliary layer in addition to the resin film. Examples of the auxiliary layer include an optical property adjusting layer (e.g., a coloring layer, an anti-reflection layer), a printing layer or a lamination layer for imparting a desired appearance, an antistatic layer, an undercoat layer, a peeling layer, and other surface treatment layers.
[0056] The main layer of the substrate disclosed herein may be the above-mentioned resin film or metal foil coated with a paint such as an acrylic-based, polyester-based, alkyd-based, melamine-based, urethane-based, acid-epoxy crosslinked paint, or a composite of these (e.g., an acrylic-melamine-based, alkyd-melamine-based paint), or may be plated with zinc or the like.
[0057] The main substrate layer according to some other preferred embodiments may be any of the following optical components: polarizing film, wavelength film, retardation film, optical compensation film, brightness enhancing film, light guide film, reflection film, anti-reflection film, hard coat (HC) film, impact absorbing film, antifouling film, photochromic film, light control film, transparent conductive film (ITO film), design film, decorative film, surface protection film, prism, lens, color filter, transparent substrate, and further, a member in which these are laminated (these may be collectively referred to as "functional film"). The above "plate" and "film" each include a plate-like, film-like, sheet-like, and other forms, and for example, "polarizing film" includes a "polarizing plate", a "polarizing sheet", and the like. The substrate layer using the above material as the main substrate layer may be used as the above-mentioned various optical components and functional films in a form having a hydrophilic layer.
[0058] In some preferred embodiments, a polarizing film (polarizing film layer) is used as the main layer of the substrate. The polarizing film may include a polarizer and a transparent protective film arranged on at least one side (preferably both sides) of the polarizer. The polarizer is not particularly limited, and may be, for example, a hydrophilic polymer film that is uniaxially stretched after adsorbing a dichroic substance such as iodine or a dichroic dye. Examples of the hydrophilic polymer film include a PVA film, a partially formalized PVA film, and an ethylene-vinyl acetate copolymer partially saponified film. Examples of the polarizer include a polyene-based oriented film such as a dehydrated PVA product or a dehydrochlorinated polyvinyl chloride product. Among these, a polarizer made of a PVA film and a dichroic substance such as iodine is preferred.
[0059] As a material for forming the transparent protective film, for example, a thermoplastic resin excellent in transparency, mechanical strength, thermal stability, moisture blocking property, isotropy, etc. is preferably used. Specific examples of such thermoplastic resins include cellulose resins such as TAC, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cycloolefin resins (typically norbornene resins), polyarylate resins, polystyrene resins, PVA resins, and mixtures of two or more of these. In some embodiments, the polarizing film has a configuration in which, for example, the polarizing film is sandwiched between two triacetyl cellulose (TAC) films. In some other preferred embodiments, a configuration in which a transparent protective film made of a thermoplastic resin such as TAC is arranged on one side of the polarizer, and a transparent protective film made of a cycloolefin resin (typically norbornene resin) or a (meth)acrylic resin is arranged on the other side may be adopted. In still another preferred embodiment, a transparent protective film made of a thermoplastic resin such as TAC is disposed on one side of the polarizer, and a thermosetting resin or an ultraviolet-curable resin such as a (meth)acrylic, urethane, acrylic urethane, epoxy, or silicone resin can be used as the transparent protective film on the other side. These transparent protective films can be laminated to the polarizer via an adhesive such as a PVA adhesive. The transparent protective film can contain one or more suitable additives depending on the purpose.
[0060] A surface treatment layer may be provided on the back surface of the polarizing film. The surface treatment layer may be provided on the transparent protective film used in the polarizing film, or may be provided on the polarizing film as a separate layer from the transparent protective film.
[0061] A suitable example of the surface treatment layer is a hard coat layer. For example, a thermoplastic resin, or a material that is cured by heat or radiation can be used as a material for forming the hard coat layer. Examples of materials that can be used include radiation curable resins such as thermosetting resins, ultraviolet curable resins, and electron beam curable resins. Among them, ultraviolet curable resins are suitable. Since ultraviolet curable resins can efficiently form a cured resin layer by a curing process by ultraviolet irradiation, they have excellent processability. As the curable resin, one or more of polyester, acrylic, urethane, amide, silicone, epoxy, melamine, etc. can be used, and these may be in a form containing a monomer, oligomer, polymer, etc. Radiation curable resins (typically ultraviolet curable resins) are particularly preferred because they do not require heat (which may cause damage to the substrate) and have excellent processing speed.
[0062] Other examples of the surface treatment layer include an anti-glare treatment layer and an anti-reflection layer for the purpose of improving visibility. An anti-glare treatment layer and an anti-reflection layer may be provided on the hard coat layer. The anti-reflection layer may have a multi-layer structure consisting of a plurality of layers. Other examples of the surface treatment layer include an anti-sticking layer. When the polarizing film disclosed herein is implemented in an embodiment having a surface treatment layer, the surface treatment layer can be made conductive by containing a conductive agent.
[0063] In an embodiment in which the substrate main layer, and in turn the substrate layer, is a polarizing film, the thickness of the polarizing film (when composed of a plurality of layers, the total thickness of the layers) is not particularly limited, and is, for example, about 1 μm or more, and is preferably about 10 μm or more or about 20 μm or more. For example, when a transparent protective film is provided, from the viewpoint of protection and the like, the thickness of the polarizing film is preferably about 30 μm or more, more preferably about 50 μm or more, and even more preferably about 70 μm or more. The upper limit of the polarizing film is not particularly limited, and is, for example, about 1 mm or less, and is preferably about 500 μm or less or about 300 μm or less. From the viewpoint of optical properties and thinning, the thickness is preferably about 150 μm or less, more preferably about 120 μm or less, and even more preferably about 100 μm or less.
[0064] Although not particularly limited, the substrate main layer disclosed herein typically does not include a glass layer such as an alkali glass plate or non-alkali glass, etc. In an embodiment using such a substrate main layer material, the effect of improving water peelability by providing a hydrophilic layer can be preferably exhibited.
[0065] The thickness of the main layer of the substrate (if there are multiple layers other than the hydrophilic layer, the total thickness of the layers other than the hydrophilic layer) is suitably 50% or more of the total thickness of the substrate layer, preferably 70% or more, more preferably 90% or more, and may be 97% or more (for example, 99% or more).
[0066] The total thickness of the substrate layer is not particularly limited and may be selected according to the purpose and mode of use of the laminate. The total thickness of the substrate layer may be, for example, about 1000 μm or less, or about 500 μm or less. From the viewpoint of weight reduction and thinning, it is appropriate to be about 300 μm or less, preferably about 150 μm or less, more preferably about 120 μm or less, may be 100 μm or less, or may be 70 μm or less. When the total thickness of the substrate layer is reduced, the flexibility of the laminate and its ability to follow the surface shape of the adherend tend to improve. In addition, from the viewpoint of handling and processability, the total thickness of the substrate layer may be, for example, 2 μm or more, or may be more than 5 μm or more than 10 μm. In some embodiments, the total thickness of the substrate layer is appropriate to be about 20 μm or more, preferably about 30 μm or more, more preferably about 50 μm or more, and even more preferably about 70 μm or more.
[0067] The surface of the base layer on the side of the adhesive layer (hence the surface of the hydrophilic layer) may be further subjected to hydrophilization treatment such as corona treatment or plasma treatment in order to further enhance hydrophilicity. The apparatus and treatment conditions used for the corona treatment or plasma treatment can be set based on conventionally known techniques so as to obtain a surface showing a desired water contact angle. In addition, the surface of the base layer on the side of the adhesive layer may be subjected to conventionally known surface treatment such as ultraviolet irradiation treatment, acid treatment, alkali treatment, etc., as necessary. Such surface treatment may be a treatment for improving the adhesion between the base layer and the adhesive layer, in other words, the anchoring property of the adhesive layer to the base layer. In addition, the surface of the base main layer (for example, the surface on the side of the hydrophilic layer) may be subjected to various surface treatments such as the above-mentioned various surface treatments, application of an undercoat agent (primer), antistatic treatment, etc. The composition of the primer is not particularly limited and can be appropriately selected from known ones. The thickness of the undercoat layer is not particularly limited, but is, for example, appropriately about 0.01 μm to 1 μm, and preferably about 0.1 μm to 1 μm.
[0068] The surface of the base layer opposite to the pressure-sensitive adhesive layer (hereinafter also referred to as the back side) may be subjected to a conventionally known surface treatment such as a release treatment, an adhesion or adhesion improving treatment, or an antistatic treatment, if necessary. For example, by surface treating the back side of the base layer with a release treatment agent, the unwinding force of the laminate wound into a roll can be reduced. As the release treatment agent, a silicone-based release treatment agent, a long-chain alkyl-based release treatment agent, an olefin-based release treatment agent, a fluorine-based release treatment agent, a fatty acid amide-based release treatment agent, molybdenum sulfide, silica powder, etc. can be used.
[0069] <Adhesive layer> (1) A layer In the laminate disclosed herein, the layer A constituting at least the surface of the adhesive layer on the substrate layer side may be an adhesive layer composed of one or more adhesives selected from various adhesives such as acrylic adhesives, rubber adhesives (natural rubber, synthetic rubber, a mixture of these, etc.), silicone adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, and fluorine adhesives. Here, the acrylic adhesive refers to an adhesive containing an acrylic polymer as the main component. The same applies to rubber adhesives and other adhesives.
[0070] (Acrylic adhesive) From the viewpoint of transparency, weather resistance, and the like, in some embodiments, an acrylic pressure-sensitive adhesive can be preferably used as the constituent material of layer A.
[0071] As the acrylic adhesive, for example, one containing an acrylic polymer constituted of a monomer component containing more than 50% by weight of (meth)acrylic acid alkyl ester having a linear or branched alkyl group having 1 to 20 carbon atoms at the ester terminal is preferable. Hereinafter, a (meth)acrylic acid alkyl ester having an alkyl group having a carbon number of X to Y at the ester terminal is referred to as "(meth)acrylic acid C X-Y It is sometimes written as "alkyl ester". Because it is easy to balance the properties, (meth)acrylic acid C is the most widely used monomer component. 1-20 The proportion of the alkyl ester may be, for example, 55% by weight or more, 60% by weight or more, or 70% by weight or more. For the same reason, the proportion of (meth)acrylic acid C among the monomer components may be 55% by weight or more, 60% by weight or more, or 70% by weight or more. 1-20 The proportion of alkyl esters may be, for example, 99.9% by weight or less, 99.5% by weight or less, or 99% by weight or less.
[0072] (Meth)acrylic acid C 1-20Non-limiting examples of alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl ... and isopropyl (meth)acrylate. Examples of such acrylates include isooctyl, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, and eicosyl (meth)acrylate.
[0073] Among these, at least (meth)acrylic acid C 4-20 It is preferable to use an alkyl ester, and at least (meth)acrylic acid C 4-18 It is more preferable to use an alkyl ester. For example, an acrylic adhesive containing one or both of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA) as the monomer component is preferable, and an acrylic adhesive containing at least 2EHA is particularly preferable. 4-20 Other examples of alkyl esters include isononyl acrylate, n-butyl methacrylate (BMA), 2-ethylhexyl methacrylate (2EHMA), isostearyl acrylate (ISTA), and the like.
[0074] In some embodiments, the monomer component constituting the acrylic polymer is (meth)acrylic acid C 4-18The monomer component may contain 40% by weight or more of alkyl ester. Thus, a monomer component containing a relatively large amount of (meth)acrylic acid alkyl ester having an alkyl group having 4 or more carbon atoms at the ester terminal tends to form an acrylic polymer having high lipophilicity. An acrylic polymer having high lipophilicity is likely to form a pressure-sensitive adhesive layer having a low rate of peel strength reduction after immersion in water. The proportion of (meth)acrylic acid C in the monomer component 4-18 The proportion of the alkyl ester may be, for example, 60% by weight or more, 70% by weight or more, 75% by weight or more, or 80% by weight or more. 6-18 The monomer component may include an alkyl ester. In addition, from the viewpoint of increasing the cohesiveness of the pressure-sensitive adhesive layer (A layer) and preventing cohesive failure, the (meth)acrylic acid C in the monomer components is 4-18 The proportion of alkyl ester is suitably 99.5% by weight or less, may be 99% by weight or less, may be 98% by weight or less, or may be 97% by weight or less. From the viewpoint of improving the cohesiveness of the pressure-sensitive adhesive layer (A layer), in some embodiments, the proportion of (meth)acrylic acid C in the monomer component is 4-18 The proportion of alkyl ester is 95% by weight or less, for example, 90% by weight or less. In some other embodiments, the proportion of (meth)acrylic acid C in the monomer component is 4-18 The proportion of the alkyl ester may be 85% by weight or less, or 75% by weight or less. 6-18 The monomer component may include an alkyl ester.
[0075] The monomer components constituting the acrylic polymer may contain, in addition to the (meth)acrylic acid alkyl ester, other monomers (copolymerizable monomers) that are copolymerizable with the (meth)acrylic acid alkyl ester, if necessary. As the copolymerizable monomer, a monomer having a polar group (e.g., a carboxy group, a hydroxyl group, a nitrogen atom-containing ring, etc.) can be suitably used. The monomer having a polar group can be useful for introducing a crosslinking point into the acrylic polymer or for increasing the cohesive strength of the adhesive. The copolymerizable monomer can be used alone or in combination of two or more kinds.
[0076] Non-limiting examples of copolymerizable monomers include the following: Carboxy group-containing monomers: for example, acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, and the like. Acid anhydride group-containing monomers: for example, maleic anhydride, itaconic anhydride. Hydroxyl group-containing monomers: for example, hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl (meth)acrylate. Monomers containing a sulfonic acid group or a phosphoric acid group: for example, styrene sulfonic acid, allyl sulfonic acid, sodium vinyl sulfonate, 2-(meth)acrylamido-2-methylpropanesulfonic acid, (meth)acrylamidopropanesulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, 2-hydroxyethyl acryloyl phosphate, etc. Epoxy group-containing monomers: for example, epoxy group-containing acrylates such as glycidyl (meth)acrylate and 2-ethyl glycidyl ether (meth)acrylate, allyl glycidyl ether, glycidyl ether (meth)acrylate, and the like. Cyano group-containing monomers: for example, acrylonitrile, methacrylonitrile, etc. Isocyanate group-containing monomers: for example, 2-isocyanatoethyl (meth)acrylate. Amide group-containing monomers: for example, (meth)acrylamide; N,N-dialkyl(meth)acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, N,N-di(n-butyl)(meth)acrylamide, and N,N-di(t-butyl)(meth)acrylamide; N-alkyl(meth)acrylamides such as N-ethyl(meth)acrylamide, N-isopropyl(meth)acrylamide, N-butyl(meth)acrylamide, and Nn-butyl(meth)acrylamide; N-vinyl carboxylic acid amides such as N-vinylacetamide; monomers having a hydroxyl group and an amide group, for example, N-(2-hydroxyethyl)(meth)acrylamide; N-hydroxyalkyl (meth)acrylamides such as N-(2-hydroxypropyl) (meth)acrylamide, N-(1-hydroxypropyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(2-hydroxybutyl) (meth)acrylamide, N-(3-hydroxybutyl) (meth)acrylamide, and N-(4-hydroxybutyl) (meth)acrylamide; monomers having an alkoxy group and an amide group, for example, N-alkoxyalkyl (meth)acrylamide such as N-methoxymethyl (meth)acrylamide, N-methoxyethyl (meth)acrylamide, and N-butoxymethyl (meth)acrylamide; and others, such as N,N-dimethylaminopropyl (meth)acrylamide and N-(meth)acryloylmorpholine. Amino group-containing monomers: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, t-butylaminoethyl (meth)acrylate. Monomers having an epoxy group: for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, allyl glycidyl ether. Monomers having a nitrogen atom-containing ring: for example, N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, N-vinylpyridazine, etc. (for example, lactams such as N-vinyl-2-caprolactam). Monomers having a succinimide skeleton: for example, N-(meth)acryloyloxymethylene succinimide, N-(meth)acryloyl-6-oxyhexamethylene succinimide, N-(meth)acryloyl-8-oxyhexamethylene succinimide, and the like. Maleimides: for example, N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, N-phenylmaleimide, and the like. Itaconimides: for example, N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexylitaconimide, N-cyclohexylitaconimide, N-laurylitaconimide, and the like. Aminoalkyl (meth)acrylates: for example, aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and t-butylaminoethyl (meth)acrylate. Alkoxy group-containing monomers: for example, alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, propoxyethyl (meth)acrylate, butoxyethyl (meth)acrylate, and ethoxypropyl (meth)acrylate; alkoxyalkylene (meth)acrylates such as methoxyethylene glycol (meth)acrylate and methoxypolypropylene glycol (meth)acrylate. Alkoxysilyl group-containing monomers: for example, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane. Vinyl esters: for example, vinyl acetate, vinyl propionate, etc. Vinyl ethers: for example, vinyl alkyl ethers such as methyl vinyl ether and ethyl vinyl ether. Aromatic vinyl compounds: for example, styrene, α-methylstyrene, vinyltoluene, etc. Olefins: for example, ethylene, butadiene, isoprene, isobutylene, etc. (Meth)acrylic acid esters having an alicyclic hydrocarbon group: for example, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, adamantyl (meth)acrylate, and the like. (Meth)acrylic acid esters having an aromatic hydrocarbon group: for example, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, benzyl (meth)acrylate, and the like. Other examples include heterocyclic ring-containing (meth)acrylates such as tetrahydrofurfuryl (meth)acrylate, halogen atom-containing (meth)acrylates such as vinyl chloride and fluorine atom-containing (meth)acrylates, silicon atom-containing (meth)acrylates such as silicone (meth)acrylate, and (meth)acrylic acid esters obtained from alcohols derived from terpene compounds.
[0077] When such a copolymerizable monomer is used, the amount of the copolymerizable monomer is not particularly limited, but is suitably 0.01% by weight or more of the total monomer components. From the viewpoint of better exerting the effect of using the copolymerizable monomer, the amount of the copolymerizable monomer may be 0.1% by weight or more of the total monomer components, or may be 0.5% by weight or more. Also, from the viewpoint of easily balancing the adhesive properties, the amount of the copolymerizable monomer is suitably 50% by weight or less of the total monomer components, and preferably 40% by weight or less.
[0078] In some embodiments, the monomer component constituting the acrylic polymer may contain a monomer having a nitrogen atom. The use of a monomer having a nitrogen atom can increase the cohesive strength of the adhesive and favorably improve the peel strength after photocuring. A suitable example of the monomer having a nitrogen atom is a monomer having a nitrogen atom-containing ring. As the monomer having a nitrogen atom-containing ring, those exemplified above can be used, and for example, a monomer represented by the general formula (1): [ka] In the general formula (1), N-vinyl cyclic amide represented by the formula: 1 is a divalent organic group, specifically -(CH2) n -. n is an integer of 2 to 7 (preferably 2, 3 or 4). Among them, N-vinyl-2-pyrrolidone can be preferably used. Another suitable example of the monomer having a nitrogen atom is (meth)acrylamide.
[0079] The amount of the monomer having a nitrogen atom (preferably a monomer having a nitrogen atom-containing ring) used is not particularly limited, and may be, for example, 1% by weight or more, 3% by weight or more, or even 5% by weight or more or 7% by weight or more of the entire monomer components. In some embodiments, the amount of the monomer having a nitrogen atom used may be 10% by weight or more, 15% by weight or more, or 20% by weight or more of the entire monomer components from the viewpoint of improving adhesive strength. In addition, the amount of the monomer having a nitrogen atom used is suitably, for example, 40% by weight or less of the entire monomer components, and may be 35% by weight or less, 30% by weight or less, or 25% by weight or less. In some other embodiments, the amount of the monomer having a nitrogen atom used may be, for example, 20% by weight or less, or 15% by weight or less of the entire monomer components.
[0080] In some embodiments, the monomer component preferably contains a carboxyl group-containing monomer. Suitable examples of the carboxyl group-containing monomer include acrylic acid (AA) and methacrylic acid (MAA). AA and MAA may be used in combination. When AA and MAA are used in combination, the weight ratio therebetween (AA / MAA) is not particularly limited and may be, for example, in the range of about 0.1 to 10. In some embodiments, the weight ratio (AA / MAA) may be, for example, about 0.3 or more, or about 0.5 or more. The weight ratio (AA / MAA) may be, for example, about 4 or less, or about 3 or less.
[0081] The use of the carboxyl group-containing monomer allows the surface of the A layer to quickly absorb an aqueous liquid such as water. This can be useful for reducing the water peeling force N2. The amount of the carboxyl group-containing monomer used may be, for example, 0.05% by weight or more, 0.1% by weight or more, 0.3% by weight or more, 0.5% by weight or more, or 0.8% by weight or more of the total monomer components. The ratio of the carboxyl group-containing monomer may be, for example, 15% by weight or less, 10% by weight or less, 5% by weight or less, 4.5% by weight or less, 3.5% by weight or less, 3.0% by weight or less, or 2.5% by weight or less. It is preferable that the amount of the carboxyl group-containing monomer used is not too large in order to suppress the diffusion of water into the bulk of the A layer and to suppress the decrease in the peel strength N1 after immersion in water. It is also advantageous that the amount of the carboxyl group-containing monomer used is not too large in order to prevent the water used in measuring the water peeling force N2 from being absorbed by the A layer and causing a shortage of water during peeling.
[0082] In some embodiments, the monomer component may include a hydroxyl group-containing monomer. The use of the hydroxyl group-containing monomer can adjust the cohesive strength and crosslink density of the adhesive and improve the peel strength N0. When the hydroxyl group-containing monomer is used, the amount of the monomer is not particularly limited, and may be, for example, 0.01% by weight or more of the total monomer components, 0.1% by weight or more, 0.5% by weight or more, 1% by weight or more, 5% by weight or more, or 10% by weight or more. In addition, from the viewpoint of suppressing excessive water diffusion into the bulk of the A layer, in some embodiments, the amount of the hydroxyl group-containing monomer is suitably, for example, 40% by weight or less of the total monomer components, and may be 30% by weight or less, 20% by weight or less, 10% by weight or less, 5% by weight or less, or 3% by weight or less. The laminate disclosed herein may also be suitably implemented in an embodiment in which a hydroxyl group-containing monomer is not substantially used as a monomer component of the adhesive layer (A layer).
[0083] In some embodiments, the monomer component may include an alkoxysilyl group-containing monomer. The alkoxysilyl group-containing monomer is typically an ethylenically unsaturated monomer having at least one (preferably two or more, for example, two or three) alkoxysilyl group in one molecule, and specific examples thereof are as described above. The above alkoxysilyl group-containing monomers can be used alone or in combination of two or more. By using the alkoxysilyl group-containing monomer, a crosslinked structure can be introduced into the pressure-sensitive adhesive layer (A layer) by condensation reaction of silanol groups (silanol condensation). The alkoxysilyl group-containing monomer can also be understood as a silane coupling agent, which will be described later.
[0084] In the embodiment in which the monomer component contains an alkoxysilyl group-containing monomer, the proportion of the alkoxysilyl group-containing monomer in the entire monomer component can be, for example, 0.005% by weight or more, and is suitably 0.01% by weight or more. In addition, from the viewpoint of improving adhesion to the adherend, the proportion of the alkoxysilyl group-containing monomer may be, for example, 0.5% by weight or less, 0.1% by weight or less, or 0.05% by weight or less.
[0085] In addition, in the monomer components of the acrylic polymer according to some preferred embodiments, the total ratio of alkoxyalkyl (meth)acrylate and alkoxypolyalkylene glycol (meth)acrylate is limited to less than 20% by weight from the viewpoint of suppressing gelation. The total ratio of the alkoxyalkyl (meth)acrylate and alkoxypolyalkylene glycol (meth)acrylate is more preferably less than 10% by weight, even more preferably less than 3% by weight, and particularly preferably less than 1% by weight, and in some embodiments, the monomer components are substantially free of alkoxyalkyl (meth)acrylate and alkoxypolyalkylene glycol (meth)acrylate (content 0 to 0.3% by weight). Similarly, the monomer component of the acrylic polymer disclosed herein may contain less than 20% by weight of an alkoxy group-containing monomer, or may contain no alkoxy group-containing monomer. The amount of the alkoxy group-containing monomer in the monomer component is preferably less than 10% by weight, more preferably less than 3% by weight, and even more preferably less than 1% by weight. In a particularly preferred embodiment, the monomer component is substantially free of an alkoxy group-containing monomer (content of 0 to 0.3% by weight).
[0086] In some preferred embodiments, the ratio of the hydrophilic monomer in the monomer component of the acrylic polymer is set to an appropriate range. This allows the water peelability to be preferably exhibited. Here, the "hydrophilic monomer" in this specification refers to a carboxyl group-containing monomer, an acid anhydride group-containing monomer, a hydroxyl group-containing monomer, a nitrogen atom-containing monomer (typically, an amide group-containing monomer such as (meth)acrylamide, a monomer having a nitrogen atom-containing ring such as N-vinyl-2-pyrrolidone), and an alkoxy group-containing monomer (typically, an alkoxyalkyl (meth)acrylate and an alkoxypolyalkylene glycol (meth)acrylate). In this embodiment, the ratio of the hydrophilic monomer in the monomer component of the acrylic polymer is suitably 40% by weight or less (e.g., 35% by weight or less), preferably 32% by weight or less, for example, 30% by weight or less, or 28% by weight or less. Although not particularly limited, the ratio of the hydrophilic monomer in the monomer component of the acrylic polymer may be 1% by weight or more, 10% by weight or more, or 20% by weight or more.
[0087] In some embodiments, the monomer component constituting the acrylic polymer may contain an alicyclic hydrocarbon group-containing (meth)acrylate. This can increase the cohesive force of the adhesive and improve the peel strength after photocuring. As the alicyclic hydrocarbon group-containing (meth)acrylate, the above-mentioned examples can be used, and for example, cyclohexyl acrylate and isobornyl acrylate can be preferably used. When an alicyclic hydrocarbon group-containing (meth)acrylate is used, the amount used is not particularly limited, and can be, for example, 1% by weight or more, 3% by weight or more, or 5% by weight or more of the entire monomer component. In some embodiments, the amount used of the alicyclic hydrocarbon group-containing (meth)acrylate may be 10% by weight or more, or 15% by weight or more of the entire monomer component. The upper limit of the amount used of the alicyclic hydrocarbon group-containing (meth)acrylate is suitably about 40% by weight or less, and may be, for example, 30% by weight or less, or 25% by weight or less (for example, 15% by weight or less, or even 10% by weight or less).
[0088] The composition of the monomer components can be set so that the glass transition temperature (hereinafter also referred to as "glass transition temperature of the polymer") calculated by the Fox formula based on the composition of the monomer components is -75°C or more and -10°C or less. In some embodiments, the glass transition temperature (Tg) of the polymer (e.g., an acrylic polymer, typically an acrylic polymer) is suitably -20°C or less, preferably -30°C or less, more preferably -40°C or less, and even more preferably -50°C or less, and may be, for example, -55°C or less. When the Tg of the polymer is lowered, the adhesion of the A layer to the base layer and the adhesion to the adherend generally tend to improve. The A layer having high adhesion to the base layer makes it easy to suppress water penetration into the interface between the base layer and the A layer in situations where peeling of the pressure-sensitive adhesive layer is not intended. This can be advantageous in terms of improving the peel strength N1 after immersion in water and reducing the peel strength reduction rate after immersion in water. From the viewpoint of facilitating an increase in the peel strength N0, the Tg of the polymer may be, for example, −70° C. or higher, or −65° C. or higher. In some other embodiments, the Tg may be, for example, −60° C. or higher, −50° C. or higher, −45° C. or higher, or −40° C. or higher.
[0089] Here, the Fox formula is a relational expression between the Tg of a copolymer and the glass transition temperature Tgi of a homopolymer obtained by homopolymerizing each of the monomers constituting the copolymer, as shown below. 1 / Tg=Σ(Wi / Tgi) In the above Fox formula, Tg represents the glass transition temperature (unit: K) of the copolymer, Wi represents the weight fraction of monomer i in the copolymer (copolymerization ratio on a weight basis), and Tgi represents the glass transition temperature (unit: K) of the homopolymer of monomer i.
[0090] The glass transition temperature of the homopolymer used to calculate Tg is a value described in a publicly known document. For example, for the monomers listed below, the following values are used as the glass transition temperatures of the homopolymers of the monomers. 2-Ethylhexyl acrylate -70℃ n-Butyl acrylate -55℃ Isostearyl acrylate -18℃ Methyl methacrylate 105℃ Methyl acrylate 8℃ Cyclohexyl acrylate 15℃ N-vinyl-2-pyrrolidone 54℃ 2-Hydroxyethyl acrylate -15℃ 4-Hydroxybutyl acrylate -40℃ Dicyclopentanyl methacrylate 175℃ Isobornyl acrylate 94℃ Acrylic acid 106℃ Methacrylic acid 228℃
[0091] For the glass transition temperatures of homopolymers of monomers other than those listed above, the values given in "Polymer Handbook" (3rd Edition, John Wiley & Sons, Inc., 1989) shall be used. When multiple values are given in this document, the highest value shall be used.
[0092] For monomers for which the glass transition temperature of the homopolymer is not described in the Polymer Handbook, the value obtained by the following measurement method shall be used (see JP 2007-51271 A). Specifically, 100 parts by weight of monomer, 0.2 parts by weight of azobisisobutyronitrile, and 200 parts by weight of ethyl acetate as a polymerization solvent are charged into a reactor equipped with a thermometer, a stirrer, a nitrogen inlet tube, and a reflux condenser, and stirred for 1 hour while passing nitrogen gas through. After removing oxygen from the polymerization system in this way, the temperature is raised to 63°C and reacted for 10 hours. Then, the mixture is cooled to room temperature to obtain a homopolymer solution with a solid concentration of 33% by weight. Then, the homopolymer solution is cast and applied onto a release liner, and dried to prepare a test sample (sheet-shaped homopolymer) with a thickness of about 2 mm. This test sample was punched out into a disk with a diameter of 7.9 mm, sandwiched between parallel plates, and subjected to a shear strain of 1 Hz using a viscoelasticity tester (ARES, Rheometrics Corporation). Viscoelasticity was measured in shear mode at a temperature range of -70 to 150°C and a heating rate of 5°C / min. The peak top temperature of tan δ was taken as the Tg of the homopolymer.
[0093] The polymer (e.g., acrylic polymer, typically an acrylic polymer) contained in the pressure-sensitive adhesive layer (A layer) disclosed herein is not particularly limited, but is preferably one having an SP value of 23.0 (MJ / m 3 ) 1 / 2 The SP value is preferably 21.0 (MJ / m or less). By adding, for example, a hydrophilic agent described below, to a pressure-sensitive adhesive containing a polymer having such an SP value, the pressure-sensitive adhesive can preferably have sufficient adhesive strength and excellent water peelability. The SP value is more preferably 21.0 (MJ / m 3 ) 1 / 2 Less than or equal to (e.g. 20.0(MJ / m 3 ) 1 / 2 The lower limit of the SP value is not particularly limited, and is, for example, about 10.0 (MJ / m 3 ) 1 / 2 More than 15.0 (MJ / m 3 ) 1 / 2 It is appropriate that the concentration is equal to or higher than 18.0 (MJ / m 3 )1 / 2 That's all.
[0094] The SP value of the above polymer was calculated by the Fedors calculation method [see Polymer Engineering and Science, Vol. 14, No. 2 (1974), pp. 148-154], that is, by the formula: SP value δ = (Σ△e / Σ△v) 1 / 2 (where Δe is the vaporization energy Δe of each atom or atomic group at 25° C., and Δv is the molar volume of each atom or atomic group at the same temperature.); A polymer having the above SP value can be obtained by appropriately determining the monomer composition based on the technical common sense of a person skilled in the art.
[0095] The adhesive layer (A layer) can be formed using an adhesive composition (hereinafter also referred to as "adhesive composition A") containing the monomer components having the above-mentioned composition in the form of a polymer, an unpolymer (i.e., a form in which the polymerizable functional group is unreacted), or a mixture thereof. The adhesive composition A can be in various forms, such as a water-dispersed adhesive composition in which an adhesive (adhesive component) is dispersed in water, a solvent-based adhesive composition in which an adhesive is contained in an organic solvent, an active energy ray-curable adhesive composition prepared to be cured by active energy rays such as ultraviolet rays or radiation to form an adhesive, or a hot melt adhesive composition that is applied in a heated and molten state and forms an adhesive when cooled to around room temperature.
[0096] In the polymerization, a known or commonly used thermal polymerization initiator or photopolymerization initiator may be used depending on the polymerization method, polymerization mode, etc. Such polymerization initiators may be used alone or in appropriate combination of two or more.
[0097] The thermal polymerization initiator is not particularly limited, and examples of the initiator that can be used include azo-based polymerization initiators, peroxide-based initiators, redox-based initiators formed by combining peroxides with reducing agents, substituted ethane-based initiators, etc. More specifically, examples of the initiator that can be used include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylpropionamidine) disulfate, 2,2'-azobis(2-amidinopropane) dihydrochloride, 2,2'-azobis[2-(5-methyl-2-imidazolin-2-yl)propane] dihydrochloride, 2,2'-azobis(N,N'-dimethyleneisobutylamidine), 2,2'-azobis[N-(2-carboxyethyl)-2-methyl Examples of initiators include, but are not limited to, azo initiators such as propionamidine hydrate; persulfates such as potassium persulfate and ammonium persulfate; peroxide initiators such as benzoyl peroxide, t-butyl hydroperoxide, and hydrogen peroxide; substituted ethane initiators such as phenyl-substituted ethane; redox initiators such as a combination of a persulfate and sodium hydrogen sulfite, and a combination of a peroxide and sodium ascorbate. Thermal polymerization can be preferably carried out at a temperature of, for example, about 20 to 100°C (typically 40 to 80°C).
[0098] The photopolymerization initiator is not particularly limited, but examples of the photopolymerization initiator that can be used include ketal-based photopolymerization initiators, acetophenone-based photopolymerization initiators, benzoin ether-based photopolymerization initiators, acylphosphine oxide-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, and thioxanthone-based photopolymerization initiators.
[0099] The amount of such a thermal polymerization initiator or photopolymerization initiator used is not particularly limited and may be a normal amount depending on the polymerization method, polymerization mode, etc. For example, about 0.001 to 5 parts by weight (typically about 0.01 to 2 parts by weight, for example about 0.01 to 1 part by weight) of the polymerization initiator can be used relative to 100 parts by weight of the monomer to be polymerized.
[0100] In the above polymerization, various conventionally known chain transfer agents (which may also be understood as molecular weight regulators or polymerization degree regulators) may be used as necessary. As the chain transfer agent, mercaptans such as n-dodecyl mercaptan, t-dodecyl mercaptan, and thioglycolic acid may be used. Alternatively, a chain transfer agent that does not contain a sulfur atom (non-sulfur chain transfer agent) may be used. Specific examples of non-sulfur chain transfer agents include anilines such as N,N-dimethylaniline and N,N-diethylaniline; terpenoids such as α-pinene and terpinolene; styrenes such as α-methylstyrene and α-methylstyrene dimer; compounds having a benzylidenyl group such as dibenzylideneacetone, cinnamyl alcohol, and cinnamylaldehyde; hydroquinones such as hydroquinone and naphthohydroquinone; quinones such as benzoquinone and naphthoquinone; olefins such as 2,3-dimethyl-2-butene and 1,5-cyclooctadiene; alcohols such as phenol, benzyl alcohol, and allyl alcohol; and benzyl hydrogens such as diphenylbenzene and triphenylbenzene. The chain transfer agent can be used alone or in combination of two or more. When using a chain transfer agent, the amount of the agent can be, for example, about 0.01 to 1 part by weight based on 100 parts by weight of the monomer component. The technology disclosed herein can also be preferably implemented in an embodiment in which no chain transfer agent is used.
[0101] The molecular weight of the polymer (e.g., acrylic polymer, typically acrylic polymer) obtained by appropriately adopting the above-mentioned various polymerization methods is not particularly limited and can be set in an appropriate range according to the required performance, etc. The weight average molecular weight (Mw) of the above-mentioned polymer is about 10 × 10 4 It is appropriate to set the value to be equal to or larger than 15×10. 4 From the viewpoint of achieving a good balance between cohesive strength and adhesive strength, it is preferable that the thickness of the adhesive layer is 30×10 4 In some embodiments, the polymer has a viscosity of preferably 40×10 or more from the viewpoint of obtaining good adhesive reliability even in a high-temperature environment. 4 or more (typically about 50×104 For example, approximately 55 x 10 4 The upper limit of the Mw of the polymer is about 500×10 4 Less than (for example, about 150 x 10 4 The Mw can be about 75×10 4 Here, Mw refers to a value calculated in terms of standard polystyrene obtained by gel permeation chromatography (GPC). As the GPC device, for example, a model named "HLC-8320GPC" (column: TSKgelGMH-H(S), manufactured by Tosoh Corporation) may be used. The same applies to the examples described later.
[0102] The laminate according to some embodiments has a layer A formed from a water-dispersed pressure-sensitive adhesive composition. A representative example of the water-dispersed pressure-sensitive adhesive composition is an emulsion-type pressure-sensitive adhesive composition. The emulsion-type pressure-sensitive adhesive composition typically contains a polymer of a monomer component and additives used as necessary.
[0103] Emulsion polymerization of monomer components is usually carried out in the presence of an emulsifier. The emulsifier for emulsion polymerization is not particularly limited, and known anionic emulsifiers, nonionic emulsifiers, etc. can be used. The emulsifier can be used alone or in combination of two or more kinds.
[0104] Non-limiting examples of anionic emulsifiers include sodium lauryl sulfate, ammonium lauryl sulfate, sodium dodecylbenzenesulfonate, sodium polyoxyethylene lauryl sulfate, sodium polyoxyethylene alkyl ether sulfate, ammonium polyoxyethylene alkyl phenyl ether sulfate, sodium polyoxyethylene alkyl phenyl ether sulfate, sodium polyoxyethylene alkyl sulfosuccinate, etc. Non-limiting examples of nonionic emulsifiers include polyoxyethylene alkyl ether, polyoxyethylene alkyl phenyl ether, polyoxyethylene fatty acid ester, polyoxyethylene polyoxypropylene block polymer, etc. Emulsifiers having reactive functional groups (reactive emulsifiers) may be used. Examples of reactive emulsifiers include radical polymerizable emulsifiers having a structure in which a radical polymerizable functional group such as a propenyl group or an allyl ether group is introduced into the above-mentioned anionic emulsifier or nonionic emulsifier.
[0105] The amount of emulsifier used in emulsion polymerization may be, for example, 0.2 parts by weight or more, 0.5 parts by weight or more, 1.0 parts by weight or more, or 1.5 parts by weight or more, relative to 100 parts by weight of monomer components. In addition, from the viewpoint of improving the peel strength N1 after water immersion, reducing the peel strength reduction rate after water immersion, or improving the transparency of the pressure-sensitive adhesive layer (A layer), in some embodiments, the amount of emulsifier used is suitably 10 parts by weight or less, preferably 5 parts by weight or less, and may be 3 parts by weight or less, relative to 100 parts by weight of monomer components. Here, the emulsifier used in emulsion polymerization may also function as a water affinity agent for A layer.
[0106] According to the emulsion polymerization, a polymerization reaction liquid in the form of an emulsion in which a polymer of a monomer component is dispersed in water is obtained. The water-dispersed PSA composition used for forming the A layer can be preferably produced using the polymerization reaction liquid.
[0107] In some preferred embodiments, the laminate may have a layer A formed from a solvent-based pressure-sensitive adhesive composition. The solvent-based pressure-sensitive adhesive composition typically contains a solution polymer of a monomer component and additives used as necessary. The effect of the technology disclosed herein (the effect of improving water peelability by forming a hydrophilic layer on the substrate layer) can be effectively exerted on the solvent-based pressure-sensitive adhesive layer (layer A). The use of a solvent-based pressure-sensitive adhesive is also advantageous in terms of optical properties. The solvent (polymerization solvent) used in solution polymerization can be appropriately selected from conventionally known organic solvents. For example, any one solvent selected from aromatic compounds such as toluene (typically aromatic hydrocarbons); esters such as ethyl acetate and butyl acetate; aliphatic or alicyclic hydrocarbons such as hexane and cyclohexane; halogenated alkanes such as 1,2-dichloroethane; lower alcohols such as isopropyl alcohol (for example, monohydric alcohols having 1 to 4 carbon atoms); ethers such as tert-butyl methyl ether; ketones such as methyl ethyl ketone; and the like, or a mixed solvent of two or more solvents can be used. According to the solution polymerization, a polymerization reaction liquid in the form of a polymer of the monomer components dissolved in a polymerization solvent is obtained. The solvent-based pressure-sensitive adhesive composition used for forming the A layer can be preferably produced using the above-mentioned polymerization reaction liquid.
[0108] In some preferred embodiments, the laminate may have a layer A formed from an active energy ray curable adhesive composition. Here, in this specification, "active energy rays" refers to energy rays having energy that can cause chemical reactions such as polymerization reactions, crosslinking reactions, and decomposition of initiators. Examples of active energy rays include light such as ultraviolet rays, visible rays, and infrared rays, and radiation such as alpha rays, beta rays, gamma rays, electron beams, neutron beams, and X-rays. A suitable example of an active energy ray curable adhesive composition is a photocurable adhesive composition. A photocurable adhesive composition has the advantage that even a thick adhesive layer can be easily formed. Among them, an ultraviolet ray curable adhesive composition is preferable. In addition, the effect of the technology disclosed herein (the effect of improving water peelability by forming a hydrophilic layer on the base layer) can be effectively exerted on the photocurable adhesive layer (layer A). In addition, the use of a photocurable adhesive is also advantageous in terms of optical properties.
[0109] Typically, the photocurable pressure-sensitive adhesive composition contains at least a part of the monomer components of the composition (which may be a part of the type of monomer or a part of the amount) in the form of a polymer. The polymerization method for forming the polymer is not particularly limited, and various conventionally known polymerization methods can be appropriately adopted. For example, thermal polymerization such as solution polymerization, emulsion polymerization, and bulk polymerization (typically carried out in the presence of a thermal polymerization initiator); photopolymerization carried out by irradiating with light such as ultraviolet rays (typically carried out in the presence of a photopolymerization initiator); radiation polymerization carried out by irradiating with radiation such as β rays and γ rays; and the like can be appropriately adopted. Among them, photopolymerization is preferred.
[0110] The photocurable pressure-sensitive adhesive composition according to some preferred embodiments contains a partial polymer of a monomer component. Such a partial polymer is typically a mixture of a polymer derived from the monomer component and an unreacted monomer, and is preferably in a syrup state (viscous liquid state). Hereinafter, a partial polymer of such a nature may be referred to as "monomer syrup" or simply as "syrup". The polymerization method for partially polymerizing the monomer component is not particularly limited, and various polymerization methods as described above can be appropriately selected and used. From the viewpoint of efficiency and simplicity, a photopolymerization method can be preferably adopted. According to photopolymerization, the polymerization conversion rate of the monomer component (monomer conversion) can be easily controlled by the polymerization conditions such as the amount of light irradiation (light amount).
[0111] The polymerization conversion rate of the monomer mixture in the partial polymer is not particularly limited. The polymerization conversion rate can be, for example, about 70% by weight or less, and is preferably about 60% by weight or less. From the viewpoint of ease of preparation and coatability of the adhesive composition containing the partial polymer, the polymerization conversion rate is suitably about 50% by weight or less, and is preferably about 40% by weight or less (for example, about 35% by weight or less). The lower limit of the polymerization conversion rate is not particularly limited, but is typically about 1% by weight or more, and is suitably about 5% by weight or more.
[0112] The adhesive composition containing the partial polymer of the monomer component can be obtained, for example, by partially polymerizing a monomer mixture containing the entire amount of the monomer component used in the preparation of the adhesive composition by an appropriate polymerization method (for example, photopolymerization method). The adhesive composition containing the partial polymer of the monomer component may be a mixture of a partial polymer or a complete polymer of a monomer mixture containing a part of the monomer component used in the preparation of the adhesive composition, and the remaining monomer component or a partial polymer thereof. In this specification, the term "complete polymer" refers to a polymerization conversion rate of more than 95% by weight.
[0113] The pressure-sensitive adhesive composition containing the partial polymer may contain other components (e.g., photopolymerization initiator, polyfunctional monomer, crosslinking agent, hydrophilic agent, etc.) that are used as needed. The method of blending such other components is not particularly limited, and for example, they may be contained in the monomer mixture in advance, or may be added to the partial polymer.
[0114] (Crosslinking agent) A crosslinking agent may be used in the pressure-sensitive adhesive layer (A layer) if necessary. In other words, the pressure-sensitive adhesive composition A for forming the pressure-sensitive adhesive layer (A layer) may contain a crosslinking agent if necessary. The crosslinking agent is typically contained in the pressure-sensitive adhesive layer (A layer) in a form after a crosslinking reaction. The pressure-sensitive adhesive layer (A layer) formed from the pressure-sensitive adhesive composition A containing a crosslinking agent typically contains a polymer (e.g., an acrylic polymer) crosslinked by the crosslinking agent. For example, the pressure-sensitive adhesive layer (A layer) may be a pressure-sensitive adhesive layer (A layer) containing an acrylic polymer crosslinked by a crosslinking agent. By using a crosslinking agent, the cohesive strength of the pressure-sensitive adhesive layer (A layer) can be appropriately adjusted, and for example, the cohesive strength of the pressure-sensitive adhesive layer (A layer) before photocuring can be appropriately adjusted. In addition, in an embodiment in which a photoreactive compound and a crosslinking agent are used in combination as described below, the properties such as adhesion durability and peel strength of the pressure-sensitive adhesive layer after photocuring can be appropriately adjusted.
[0115] The type of crosslinking agent is not particularly limited, and can be selected from conventionally known crosslinking agents so that the crosslinking agent exerts an appropriate crosslinking function in the adhesive layer, for example, according to the composition of the adhesive composition. Examples of crosslinking agents that can be used include isocyanate-based crosslinking agents, epoxy-based crosslinking agents, oxazoline-based crosslinking agents, aziridine-based crosslinking agents, carbodiimide-based crosslinking agents, melamine-based crosslinking agents, urea-based crosslinking agents, metal alkoxide-based crosslinking agents, metal chelate-based crosslinking agents, metal salt-based crosslinking agents, hydrazine-based crosslinking agents, and amine-based crosslinking agents. These can be used alone or in combination of two or more. In the water-dispersed adhesive composition, it is preferable to use a crosslinking agent that is soluble or dispersible in water.
[0116] As the isocyanate-based crosslinking agent, a polyfunctional isocyanate compound having two or more functionalities can be used. For example, aromatic isocyanates such as tolylene diisocyanate, xylene diisocyanate, polymethylene polyphenyl diisocyanate, tris(p-isocyanatophenyl)thiophosphate, diphenylmethane diisocyanate, etc., alicyclic isocyanates such as isophorone diisocyanate, etc., aliphatic isocyanates such as hexamethylene diisocyanate, etc. can be mentioned. Examples of commercially available products include isocyanate adducts such as trimethylolpropane / tolylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, product name "Coronate L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Tosoh Corporation, product name "Coronate HL"), isocyanurate of hexamethylene diisocyanate (manufactured by Tosoh Corporation, product name "Coronate HX"), and trimethylolpropane / xylylene diisocyanate adduct (manufactured by Mitsui Chemicals, product name "Takenate D-110N"), etc. In the water-dispersible pressure-sensitive adhesive composition, it is preferable to use an isocyanate-based crosslinking agent that is soluble or dispersible in water. For example, a water-soluble, water-dispersible or self-emulsifying isocyanate-based crosslinking agent can be preferably used. A so-called blocked isocyanate-based isocyanate-based crosslinking agent in which the isocyanate group is blocked can be preferably used.
[0117] As the epoxy crosslinking agent, those having two or more epoxy groups in one molecule can be used without any particular limitation. An epoxy crosslinking agent having 3 to 5 epoxy groups in one molecule is preferable. Specific examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, 1,6-hexanediol diglycidyl ether, polyethylene glycol diglycidyl ether, polyglycerol polyglycidyl ether, and the like. Commercially available epoxy crosslinking agents include Mitsubishi Gas Chemical Company's product names "TETRAD-X" and "TETRAD-C", DIC Corporation's product name "Epicron CR-5L", Nagase ChemteX Corporation's product name "Denacol EX-512", Nissan Chemical Industries' product name "TEPIC-G", and the like.
[0118] As the oxazoline-based crosslinking agent, any agent having one or more oxazoline groups in one molecule can be used without any particular limitation. Examples of the aziridine crosslinking agent include trimethylolpropane tris[3-(1-aziridinyl)propionate], trimethylolpropane tris[3-(1-(2-methyl)aziridinylpropionate)], and the like. As the carbodiimide crosslinking agent, a low molecular weight compound or a high molecular weight compound having two or more carbodiimide groups can be used.
[0119] In some embodiments, peroxides may be used as crosslinking agents. Examples of peroxides include di(2-ethylhexyl)peroxydicarbonate, di(4-t-butylcyclohexyl)peroxydicarbonate, di-sec-butylperoxydicarbonate, t-butylperoxyneodecanoate, t-hexylperoxypivalate, t-butylperoxypivalate, dilauroylperoxide, di-n-octanoylperoxide, 1,1,3,3-tetramethylbutylperoxyisobutyrate, and dibenzoylperoxide. Among these, examples of peroxides that are particularly excellent in crosslinking reaction efficiency include di(4-t-butylcyclohexyl)peroxydicarbonate, dilauroylperoxide, and dibenzoylperoxide. In addition, when peroxides are used as the polymerization initiator, it is also possible to use the remaining peroxides that are not used in the polymerization reaction in the crosslinking reaction. In this case, the remaining amount of peroxide is quantified, and if the ratio of peroxide is less than the predetermined amount, peroxide is added as necessary to reach the predetermined amount. The amount of peroxide can be quantified by the method described in Japanese Patent No. 4971517.
[0120] When a crosslinking agent is used, the amount used (when two or more crosslinking agents are used, the total amount of the crosslinking agents) is not particularly limited. From the viewpoint of realizing a pressure-sensitive adhesive that exhibits well-balanced adhesive properties such as adhesive strength and cohesive strength, the amount of the crosslinking agent used is suitably about 5 parts by weight or less relative to 100 parts by weight of the monomer component (e.g., the monomer component of an acrylic polymer) contained in the pressure-sensitive adhesive composition A, and may be 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or less than 1 part by weight. From the viewpoint of favorably exhibiting the effect of the combined use with the photoreactive compound, in some embodiments, the amount of the crosslinking agent (e.g., an isocyanate-based crosslinking agent) used relative to 100 parts by weight of the monomer component may be, for example, 0.50 parts by weight or less, 0.40 parts by weight or less, 0.30 parts by weight or less, or 0.20 parts by weight or less. The lower limit of the amount of the crosslinking agent used is not particularly limited, and may be more than 0 parts by weight relative to 100 parts by weight of the monomer component. In some embodiments, the amount of the crosslinking agent used can be, for example, 0.001 parts by weight or more, optionally 0.01 parts by weight or more, optionally 0.05 parts by weight or more, or optionally 0.10 parts by weight or more, relative to 100 parts by weight of the monomer component.
[0121] A crosslinking catalyst may be used to promote the crosslinking reaction more effectively. Examples of the crosslinking catalyst include metal-based crosslinking catalysts such as tetra-n-butyl titanate, tetraisopropyl titanate, nursem ferric, butyltin oxide, and dioctyltin dilaurate. Among them, tin-based crosslinking catalysts such as dioctyltin dilaurate are preferred. The amount of the crosslinking catalyst used is not particularly limited. The amount of the crosslinking catalyst used can be, for example, about 0.0001 parts by weight or more, about 0.001 parts by weight or more, about 0.005 parts by weight or more, and can be about 1 part by weight or less, about 0.1 parts by weight or less, about 0.05 parts by weight or less, relative to 100 parts by weight of the monomer component (for example, the monomer component of the acrylic polymer) contained in the adhesive composition A.
[0122] The adhesive composition A used for forming the adhesive layer (A layer) can contain a compound that generates keto-enol tautomerism as a crosslinking retarder, if desired. For example, a compound that generates keto-enol tautomerism can be preferably used in the adhesive composition A containing an isocyanate-based crosslinking agent or the adhesive composition A that can be used by blending an isocyanate-based crosslinking agent. This can provide an effect of extending the pot life of the adhesive composition. As the compound that generates keto-enol tautomerism, various β-dicarbonyl compounds can be used. Specific examples include β-diketones such as acetylacetone and 2,4-hexanedione; acetoacetates such as methyl acetoacetate and ethyl acetoacetate; propionyl acetates such as ethyl propionyl acetate; isobutyryl acetates such as ethyl isobutyryl acetate; malonates such as methyl malonate and ethyl malonate; and the like. Among them, acetylacetone and acetoacetates are preferred. The compound that generates keto-enol tautomerism can be used alone or in combination of two or more. The amount of the compound that causes keto-enol tautomerization used may be, for example, 0.1 parts by weight or more and 20 parts by weight or less, and suitably 0.5 parts by weight or more and 15 parts by weight or less, for example, 1 part by weight or more and 10 parts by weight or less, or may be 1 part by weight or more and 5 parts by weight or less, relative to 100 parts by weight of the monomer component (e.g., the monomer component of an acrylic polymer) contained in the adhesive composition A.
[0123] (Photoreactive compound) The technology disclosed herein can be implemented in a form that satisfies the predetermined peel strength characteristics and water peel strength reduction rate characteristics, regardless of whether the adhesive layer is a photocurable adhesive layer (adhesive layer in a state that can be photocured) or a photocurable adhesive layer (adhesive layer after photocuring). In such a form, the adhesive composition A for forming the adhesive layer (A layer) may contain a photoreactive compound. In some embodiments, the adhesive layer (A layer) may contain a photoreactive compound. As the photoreactive compound, a compound having two or more ethylenically unsaturated groups in the molecule is used. In addition, some preferred embodiments of the photoreactive compound have two or more ethylenically unsaturated groups and an oxyalkylene structural unit in the molecule. The photoreactive compound contained in the adhesive layer (A layer) can form a crosslinked structure having appropriate flexibility by reacting the ethylenically unsaturated groups by irradiation with light (e.g., ultraviolet light) after laminating the adhesive layer (A layer) on the base layer. Therefore, in some embodiments, the photoreactive compound may be present in the pressure-sensitive adhesive layer (A layer) in a reacted state. In other embodiments, the photoreactive compound may be present in the pressure-sensitive adhesive layer (A layer) in a free state (may be unreacted) as described below. This makes it possible to effectively improve durability while suppressing a decrease in the peel strength (anchoring ability) of the pressure-sensitive adhesive layer (A layer) to the base layer. The photoreactive compound may be used alone or in combination of two or more.
[0124] Examples of the ethylenically unsaturated group include, but are not limited to, acryloyl group, methacryloyl group, vinyl group and allyl group.Two or more ethylenically unsaturated groups that a photoreactive compound has in a molecule may be the same group, or may be two or more different groups.Acryloyl group and methacryloyl group are preferred ethylenically unsaturated groups from the viewpoint of photoreactivity.Among them, acryloyl group is preferred.
[0125] The oxyalkylene structural unit (AO unit) refers to a structural unit represented by the general formula (U1): -AO-; and typically represents a structural unit represented by the general formula (U2): -C m H 2mO-;. Here, A in the above general formula (U1) is typically an alkylene group having 2 or more carbon atoms, and preferably an alkylene group having 2 to 4 carbon atoms. m in the above formula (U2) is an integer of 2 or more, preferably an integer of 2 to 4, and more preferably an integer of 2 to 3. Suitable examples of the AO unit include an oxyethylene unit and an oxypropylene unit. Such an AO unit can be formed, for example, by modification (addition reaction) with an alkylene oxide or an alkylene glycol.
[0126] The photoreactive compound has a repeating structure in which two or more AO units represented by the above general formula (U1) are consecutively formed, i.e., a compound represented by the general formula: -(AO) n -;. In the above formula, n is an integer of 2 or more, for example, an integer of 2 to 10, preferably an integer of 2 to 5, and more preferably an integer of 2 to 3. Alternatively, the photoreactive compound may be a compound that does not contain a repeating structure in which two or more AO units are consecutive (it may be a compound that contains two or more AO units discontinuously). With such a photoreactive compound, a pressure-sensitive adhesive layer (layer A) having a good balance between cohesiveness and crosslinking flexibility can be efficiently formed.
[0127] It is more preferable that the photoreactive compound has a molecular structure in which at least one, preferably two or more (for example, about 2 to 4) AO units are arranged between one ethylenically unsaturated group and any other ethylenically unsaturated group. The two or more AO units are adjacent to each other and have -(AO) n - They may form a structure or may not be adjacent to each other. In some embodiments, the photoreactive compound preferably has a molecular structure in which AO units are arranged adjacent to at least a part of the ethylenically unsaturated groups contained in the photoreactive compound.It is considered that the AO units arranged adjacent to the ethylenically unsaturated groups (e.g., (meth)acryloyl groups) can effectively contribute to the softening of the crosslinked structure formed by the reaction of the ethylenically unsaturated groups.In some embodiments, a photoreactive compound can be preferably adopted in which AO units are arranged adjacent to 50% by number or more, more preferably 75% by number or more, for example, substantially 100% by number of the ethylenically unsaturated groups contained in the molecule.
[0128] As the photoreactive compound, a compound having 2 to 10 ethylenically unsaturated groups in a molecule is preferred, a compound having 2 to 8 ethylenically unsaturated groups in a molecule is more preferred, and a compound having 2 to 6 ethylenically unsaturated groups in a molecule is even more preferred. In some embodiments, a compound having 3 or more (typically 3 to 8, for example 3 to 6) ethylenically unsaturated groups in a molecule can be used as the photoreactive compound. By incorporating a photoreactive compound having 3 or more ethylenically unsaturated groups in a molecule in the pressure-sensitive adhesive layer (A layer), the durability of adhesion to the base layer after curing of the pressure-sensitive adhesive layer (A layer) can be efficiently improved (for example, sufficiently improved even with a relatively small amount of the photoreactive compound). This can be advantageous from the viewpoint of the processability, handling, etc. of the laminate disclosed herein. In some other embodiments, a compound having 2 ethylenically unsaturated groups in a molecule can be used as the photoreactive compound. This can realize a pressure-sensitive adhesive exhibiting higher peel strength. In some preferred embodiments, a compound having three or more (typically 3 to 8, for example 3 to 6) ethylenically unsaturated groups in the molecule and a compound having two ethylenically unsaturated groups in the molecule are used in combination as the photoreactive compound.
[0129] Examples of photoreactive compounds having three or more ethylenically unsaturated groups in the molecule include, but are not limited to, ethoxylated pentaerythritol tri(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, ethoxylated dipentaerythritol penta(meth)acrylate, ethoxylated dipentaerythritol hexa(meth)acrylate, ethylene oxide (EO)-modified trimethylolpropane tri(meth)acrylates such as trimethylolpropane trioxyethyl (meth)acrylate and trimethylolpropane polyoxyethyl (meth)acrylate, propylene oxide (PO)-modified trimethylolpropane tri(meth)acrylates such as trimethylolpropane trioxypropyl (meth)acrylate and trimethylolpropane polyoxypropyl (meth)acrylate, and the like. Examples of photoreactive compounds having two ethylenically unsaturated groups in the molecule include, but are not limited to, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, EO-modified bisphenol A di(meth)acrylate, EO-modified bisphenol F di(meth)acrylate, PO-modified bisphenol A di(meth)acrylate, and PO-modified bisphenol F di(meth)acrylate.
[0130] The molecular weight of the photoreactive compound is not particularly limited and may be selected so that the desired effect is suitably exhibited. For example, the photoreactive compound may have a molecular weight of about 2500 or less. From the viewpoint of ease of preparation of the pressure-sensitive adhesive composition A, in some embodiments, the molecular weight of the photoreactive compound may be, for example, 2000 or less, 1500 or less, or 1000 or less. The molecular weight of the photoreactive compound is typically 200 or more. From the viewpoint of processability, handling, etc., in some embodiments, the molecular weight of the photoreactive compound may be, for example, 230 or more, 300 or more, 350 or more, 450 or more, 500 or more, or 550 or more. The molecular weight of the photoreactive compound can be obtained as a weight average molecular weight (Mw) converted into standard polystyrene by, for example, a GPC method. Alternatively, the molecular weight of the photoreactive compound may be a nominal value provided by the manufacturer or a molecular weight calculated from the molecular structure.
[0131] The amount of the photoreactive compound contained in the pressure-sensitive adhesive layer (A layer) is not particularly limited and can be appropriately set according to the desired performance. In some embodiments, the content of the photoreactive compound in the pressure-sensitive adhesive composition A or the pressure-sensitive adhesive layer (A layer) may be, for example, 0.5 parts by weight or more, suitably 1 part by weight or more, 2 parts by weight or more, 3 parts by weight or more, or 4 parts by weight or more, relative to 100 parts by weight of the monomer component of the polymer (typically an acrylic polymer, for example an acrylic polymer) contained in the pressure-sensitive adhesive layer (A layer). By increasing the content of the photoreactive compound, the adhesion durability of the pressure-sensitive adhesive layer (A layer) to the base layer after photocuring tends to improve. In addition, the content of the photoreactive compound relative to 100 parts by weight of the monomer component can be, for example, 30 parts by weight or less, and from the viewpoint of processability, etc., it is suitable to set it to less than 20 parts by weight, and it is preferable to set it to less than 15 parts by weight. In order to avoid a decrease in peel strength due to excessive crosslinking, in some embodiments, the content of the photoreactive compound relative to 100 parts by weight of the above monomer component may be, for example, less than 10 parts by weight, less than 8.0 parts by weight, or less than 6.0 parts by weight.
[0132] The photoreactive compound is present in a free form in the pressure-sensitive adhesive composition A before the pressure-sensitive adhesive layer (A layer) is formed and in the photocurable pressure-sensitive adhesive layer (A layer), and is preferably chemically bonded to other components (e.g., acrylic polymers) in the pressure-sensitive adhesive layer after photocuring. The chemical bond can be formed, for example, by a reaction between a functional group F1 other than an ethylenically unsaturated group contained in the molecule of the photoreactive compound and a functional group F2 that is a functional group contained in the molecule of the other component and is capable of reacting with the functional group F1. The reaction can be suitably advanced, for example, by having a photoreactive catalyst described below present in the pressure-sensitive adhesive layer (A layer) and performing a photocuring treatment. Such a pressure-sensitive adhesive layer (A layer) can be suitably formed using a pressure-sensitive adhesive composition A containing the photoreactive compound in a free form. Here, the term "free form" refers to the fact that the photoreactive compound is not chemically bonded to other components (e.g., acrylic polymers) contained in the pressure-sensitive adhesive layer (A layer) or the pressure-sensitive adhesive composition A. The pressure-sensitive adhesive composition A containing the photoreactive compound in a free form can be advantageous from the standpoint of ease of preparation and inhibition of gelation.
[0133] The adhesive composition A and the photocurable adhesive layer (A layer) may contain one or more other photoreactive compounds that have two or more ethylenically unsaturated groups in the molecule and are not photoreactive compounds. Examples of other photoreactive compounds include compounds that have two or more ethylenically unsaturated groups in the molecule and do not have AO-units; compounds that have two or more ethylenically unsaturated groups in the molecule, the molecular weight per ethylenically unsaturated group is greater than 250, and the compound has an AO unit; compounds that have two or more ethylenically unsaturated groups in the molecule, the molecular weight per ethylenically unsaturated group is greater than 250, and the compound has no AO unit; and the like. Specific examples of compounds corresponding to other photoreactive compounds include pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, trimethylolethane tri(meth)acrylate, tetramethylolmethane tri(meth)acrylate, tris(2-hydroxyethyl)acrylate, Diethyl) isocyanurate di(meth)acrylate, tris(2-hydroxyethyl) isocyanurate tri(meth)acrylate, neopentyl glycol di(meth)acrylate, hydroxypivalic acid neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, allyl (meth)acrylate, vinyl (meth)acrylate, divinylbenzene, hydroquinone di(meth)acrylate, resorcinol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, etc. are included, but are not limited thereto. The content of other photoreactive compounds in the adhesive composition A or the adhesive layer (A layer) is not particularly limited. In some embodiments, the content of other photoreactive compounds in the pressure-sensitive adhesive composition A or the pressure-sensitive adhesive layer (layer A) may be, for example, 0.01 parts by weight or more, suitably 0.1 parts by weight or more, or may be 1 part by weight or more, relative to 100 parts by weight of the monomer component of the polymer (typically an acrylic polymer, for example an acrylic polymer) contained in the pressure-sensitive adhesive layer (layer A).The content of the other photoreactive compound relative to 100 parts by weight of the monomer component can be, for example, 10 parts by weight or less, suitably less than 5 parts by weight, and preferably less than 3 parts by weight. In an embodiment in which the photoreactive compound is used in combination with the other photoreactive compound, the content of the other photoreactive compound in the pressure-sensitive adhesive composition A or the pressure-sensitive adhesive layer (A layer) may be, for example, 0.9 times or less of the content of the photoreactive compound, suitably 0.5 times or less, may be 0.2 times or less, or may be 0.1 times or less, on a weight basis. The technology disclosed herein may be implemented in a form in which the pressure-sensitive adhesive composition A or the pressure-sensitive adhesive layer (A layer) does not substantially contain other photoreactive compounds. Here, "substantially not containing other photoreactive compounds" means that at least other photoreactive compounds are not used intentionally, and for example, it is acceptable for a small amount of compounds corresponding to other photoreactive compounds to be unintentionally mixed in as impurities or subcomponents in the materials used to prepare the pressure-sensitive adhesive composition A. The other photoreactive compounds are present in a free form in the adhesive composition A and in the photocurable adhesive layer (A layer) before the adhesive layer (A layer) is formed, and are preferably chemically bonded to other components (e.g., acrylic polymers) in the adhesive layer in the photocured adhesive layer (A layer).
[0134] (Photoreaction catalyst) The adhesive composition A and the photocurable adhesive layer (A layer) disclosed herein may contain a photoreaction catalyst (photoreaction initiator) as necessary for the purpose of improving or imparting photocurability. Examples of the photoreaction catalyst include ketal-based photoreaction initiators, acetophenone-based photoreaction initiators, benzoin ether-based photoreaction initiators, acylphosphine oxide-based photoreaction initiators, α-ketol-based photoreaction initiators, aromatic sulfonyl chloride-based photoreaction initiators, photoactive oxime-based photoreaction initiators, benzoin-based photoreaction initiators, benzyl-based photoreaction initiators, benzophenone-based photoreaction initiators, and thioxanthone-based photoreaction initiators. The photoreaction catalyst may be used alone or in appropriate combination of two or more.
[0135] Specific examples of ketal photoinitiators include 2,2-dimethoxy-1,2-diphenylethan-1-one, and the like. Specific examples of acetophenone-based photoinitiators include 1-hydroxycyclohexyl-phenyl-ketone, 4-phenoxydichloroacetophenone, 4-t-butyl-dichloroacetophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, 2-hydroxy-2-methyl-1-phenyl-propan-1-one, methoxyacetophenone, and the like. Specific examples of benzoin ether photoinitiators include benzoin ethers such as benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and substituted benzoin ethers such as anisole methyl ether. Specific examples of acylphosphine oxide photoinitiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide, and the like. Specific examples of α-ketol photoinitiators include 2-methyl-2-hydroxypropiophenone, 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one, etc. Specific examples of aromatic sulfonyl chloride photoinitiators include 2-naphthalenesulfonyl chloride, etc. Specific examples of photoactive oxime photoinitiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime, etc. Specific examples of benzoin photoinitiators include benzoin, etc. Specific examples of benzyl photoinitiators include benzyl, etc. Specific examples of benzophenone-based photoinitiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, polyvinylbenzophenone, α-hydroxycyclohexyl phenyl ketone, and the like. Specific examples of thioxanthone-based photoinitiators include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-dichlorothioxanthone, 2,4-diethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, dodecylthioxanthone, and the like.
[0136] The content of the photoreactive catalyst in the pressure-sensitive adhesive layer (A layer) is not particularly limited and can be set so that the desired effect is appropriately exhibited. In some embodiments, the content of the photoreactive catalyst can be, for example, about 0.005 parts by weight or more, suitably 0.01 parts by weight or more, preferably 0.05 parts by weight or more, may be 0.10 parts by weight or more, may be 0.15 parts by weight or more, or may be 0.20 parts by weight or more, relative to 100 parts by weight of the monomer component of the polymer (typically an acrylic polymer) contained in the pressure-sensitive adhesive layer. By increasing the content of the photoreactive catalyst, the photocurability of the pressure-sensitive adhesive layer (A layer) is improved. In addition, the content of the photoreactive catalyst relative to 100 parts by weight of the monomer component is suitably 5 parts by weight or less, preferably 2 parts by weight or less, may be 1 part by weight or less, may be 0.7 parts by weight or less, or may be 0.5 parts by weight or less. It may be advantageous from the viewpoint of improving the storage stability (for example, stability against photodegradation) of the laminate when the content of the photoreactive catalyst is not too high.
[0137] The pressure-sensitive adhesive layer (A layer) containing a photoreactive catalyst can typically be formed using a pressure-sensitive adhesive composition A (e.g., a solvent-based pressure-sensitive adhesive composition) containing the photoreactive catalyst. The pressure-sensitive adhesive composition containing a photoreactive catalyst can be prepared, for example, by mixing the photoreactive catalyst with other components used in the composition. In addition, when preparing a pressure-sensitive adhesive composition using a polymer (typically an acrylic polymer) synthesized (photopolymerized) in the presence of a photopolymerization initiator, the residue (unreacted material) of the photopolymerization initiator used in synthesizing the polymer may be used as part or all of the photoreactive catalyst contained in the pressure-sensitive adhesive layer (A layer). The same applies when using an acrylic oligomer synthesized in the presence of a photopolymerization initiator as an optional acrylic oligomer. From the viewpoint of ease of production management, the pressure-sensitive adhesive layer (A layer) disclosed herein can be preferably formed using a pressure-sensitive adhesive composition prepared by newly adding the above-mentioned amount of photoreactive catalyst to other components.
[0138] (Water compatibility agent) The adhesive composition A that can be used in the adhesive layer (A layer) in the technology disclosed herein can contain a hydrophilic agent, if desired. By containing a hydrophilic agent in the adhesive layer (A layer), the peeling force can be effectively reduced by utilizing an aqueous liquid such as water. The reason for this is not particularly limited, but it is generally believed that a hydrophilic agent has a hydrophilic region and is therefore likely to be unevenly distributed on the surface of the adhesive layer (A layer) (e.g., an adhesive layer formed from a solvent-based adhesive composition), thereby exerting an effect of efficiently increasing the water affinity of the adhesive layer (A layer) surface, and effectively reducing the peeling force when the adhesive layer (A layer) comes into contact with water.
[0139] As the hydrophilic agent, one that is liquid at room temperature (about 25° C.) can be preferably used from the viewpoint of ease of preparation of the pressure-sensitive adhesive composition, etc. The hydrophilic agent can be used alone or in combination of two or more kinds.
[0140] In some embodiments, the hydrophilic agent can be at least one compound A selected from surfactants and compounds having polyoxyalkylene skeletons.As surfactants and compounds having polyoxyalkylene skeletons, one or more of known surfactants and compounds having polyoxyalkylene skeletons can be used without any particular restrictions.It is to be noted that among the above surfactants, there are compounds having polyoxyalkylene skeletons, and it goes without saying that the same is true in reverse.
[0141] As the surfactant that can be used as compound A, known nonionic surfactants, anionic surfactants, cationic surfactants, etc. can be used. Among them, nonionic surfactants are preferable. The surfactants can be used alone or in combination of two or more.
[0142] Examples of nonionic surfactants include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, and polyoxyethylene oleyl ether; polyoxyethylene alkyl phenyl ethers such as polyoxyethylene octyl phenyl ether and polyoxyethylene nonyl phenyl ether; sorbitan monolaurate, sorbitan monopalmitate, sorbitan monostearate, and sorbitan monooleate; polyoxyethylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan tristearate, polyoxyethylene sorbitan triisostearate, polyoxyethylene sorbitan monooleate, and polyoxyethylene sorbitan trioleate; polyoxyethylene glyceryl ether fatty acid esters; polyoxyethylene-polyoxypropylene block copolymers; and the like. These nonionic surfactants can be used alone or in combination of two or more.
[0143] Examples of anionic surfactants include alkylbenzene sulfonates such as nonylbenzene sulfonate and dodecylbenzene sulfonate (e.g., sodium dodecylbenzene sulfonate); alkyl sulfates such as lauryl sulfate (e.g., sodium lauryl sulfate, ammonium lauryl sulfate) and octadecyl sulfate; fatty acid salts; polyoxyethylene alkyl ether sulfates such as polyoxyethylene octadecyl ether sulfate and polyoxyethylene lauryl ether sulfate (e.g., sodium polyoxyethylene alkyl ether sulfate); polyoxyethylene alkyl phenyl ether sulfates such as polyoxyethylene lauryl phenyl ether sulfate (e.g., polyoxyethylene alkyl phenyl ether ammonium sulfate); Examples of the anionic surfactant include polyether sulfates such as sodium, polyoxyethylene alkylphenyl ether sulfate, polyoxyethylene styrenated phenyl ether sulfate, etc.; polyoxyethylene alkyl ether phosphates such as polyoxyethylene stearyl ether phosphate and polyoxyethylene lauryl ether phosphate; polyoxyethylene alkyl ether phosphate salts such as sodium salts and potassium salts of the above polyoxyethylene alkyl ether phosphates; sulfosuccinates such as lauryl sulfosuccinate and polyoxyethylene lauryl sulfosuccinate (for example, sodium polyoxyethylene alkyl sulfosuccinate); polyoxyethylene alkyl ether acetates; and the like. When the anionic surfactant forms a salt, the salt may be, for example, a metal salt (preferably a salt of a monovalent metal) such as sodium salt, potassium salt, calcium salt, magnesium salt, etc., an ammonium salt, an amine salt, etc. The anionic surfactant may be used alone or in combination of two or more.
[0144] In some embodiments, for example, an anionic surfactant having at least one of a -POH group, a -COH group, and a -SOH group may be preferably used. Among them, a surfactant having a -POH group is preferable. Such a surfactant typically contains a phosphate ester structure, and may be, for example, a monoester of phosphoric acid (ROP(=O)(OH)2; where R is a monovalent organic group), a diester ((RO)2P(=O)OH; where R is the same or different monovalent organic group), a mixture containing both a monoester and a diester, etc. A suitable example of a surfactant having a -POH group is a polyoxyethylene alkyl ether phosphate ester. The number of carbon atoms of the alkyl group in the polyoxyethylene alkyl ether phosphate ester may be, for example, 6 to 20, 8 to 20, 10 to 20, 12 to 20, or 14 to 20.
[0145] Examples of the cationic surfactant include polyether amines such as polyoxyethylene laurylamine, polyoxyethylene stearylamine, etc. The cationic surfactants may be used alone or in combination of two or more.
[0146] Examples of compounds having a polyoxyalkylene skeleton that can be used as compound A include polyalkylene glycols such as polyethylene glycol (PEG) and polypropylene glycol (PPG); polyethers containing polyoxyethylene units, polyethers containing polyoxypropylene units, compounds containing oxyethylene units and oxypropylene units (these units may be arranged randomly or in blocks); and derivatives thereof. Also, among the above-mentioned surfactants, compounds having a polyoxyalkylene skeleton can be used. These can be used alone or in combination of two or more. Among them, it is preferable to use a compound having a polyoxyethylene skeleton (also called a polyoxyethylene segment), and PEG is more preferable.
[0147] The molecular weight (chemical formula weight) of the compound having a polyoxyalkylene skeleton (e.g., polyethylene glycol) is not particularly limited, and is suitably less than 1000, and from the viewpoint of the preparation of the adhesive composition, is preferably about 600 or less (e.g., 500 or less). The lower limit of the molecular weight of the compound having a polyoxyalkylene skeleton (e.g., polyethylene glycol) is not particularly limited, and those having a molecular weight of about 100 or more (e.g., about 200 or more, further about 300 or more) are preferably used.
[0148] Other examples of the hydrophilic agent include water-soluble polymers such as polyvinyl alcohol, polyvinylpyrrolidone, and polyacrylic acid. The water-soluble polymers can be used alone or in combination of two or more. In the technology disclosed herein, the hydrophilic agent can be one or two or more of compound A, one or two or more of water-soluble polymers, or a combination of these.
[0149] The HLB of the water affinity agent is not particularly limited, and may be, for example, 3 or more, suitably about 6 or more, and may be 8 or more (for example, 9 or more). In some preferred embodiments, the HLB of the water affinity agent is 10 or more. This tends to favorably develop water peelability. The HLB is more preferably 11 or more, even more preferably 12 or more, and particularly preferably 13 or more (for example, 14 or more). By including a water affinity agent (typically a surfactant) having an HLB in the above range in layer A, water peelability can be more effectively developed. The upper limit of the HLB is 20 or less, and may be, for example, 18 or less, 16 or less, or 15 or less.
[0150] In this specification, HLB is the hydrophilic-lipophilic balance according to Griffin, which is a value indicating the degree of affinity of a surfactant to water or oil, and is a ratio of hydrophilicity to lipophilicity expressed as a number between 0 and 20. The definition of HLB is as described in WC Griffin: J. Soc. Cosmetic Chemists, 1, 311 (1949), Takahashi Kotami, Namba Yoshiro, Koike Motoo, and Kobayashi Masao, "Surfactant Handbook", 3rd Edition, Kogaku Toshosha Publishing, November 25, 1972, pp. 179-182, etc. The hydrophilic agent having the above HLB can be selected based on the technical common sense of a person skilled in the art, by referring to the above references as necessary.
[0151] Such a hydrophilic agent is preferably contained in a free form in layer A. From the viewpoint of ease of preparation of the pressure-sensitive adhesive composition, a hydrophilic agent that is liquid at room temperature (about 25° C.) is preferably used.
[0152] The A layer containing a hydrophilic agent is typically formed from a pressure-sensitive adhesive composition A containing a hydrophilic agent. The pressure-sensitive adhesive composition A may be any of the above-mentioned water-dispersible pressure-sensitive adhesive composition, solvent-based pressure-sensitive adhesive composition, active energy ray-curable pressure-sensitive adhesive composition, hot-melt pressure-sensitive adhesive composition, etc. In some preferred embodiments, the A layer containing a hydrophilic agent may be a pressure-sensitive adhesive layer formed from a photocurable or solvent-based pressure-sensitive adhesive composition A. In such a layer A, the effect of adding a hydrophilic agent can be preferably exhibited. The A layer may have photocurability.
[0153] The content of the hydrophilic agent in the A layer is not particularly limited, and can be set so that the use effect of the hydrophilic agent is appropriately exhibited. In some embodiments, the content of the hydrophilic agent can be, for example, 0.001 parts by weight or more, suitably 0.01 parts by weight or more, may be 0.03 parts by weight or more, may be 0.07 parts by weight or more, or may be 0.1 parts by weight or more, per 100 parts by weight of the monomer component constituting the polymer (e.g., acrylic polymer) contained in the A layer. In some preferred embodiments, the content of the hydrophilic agent can be, for example, 0.2 parts by weight or more, per 100 parts by weight of the monomer component, and from the viewpoint of obtaining a higher effect, may be 0.5 parts by weight or more, may be 1.0 parts by weight or more, or may be 1.5 parts by weight or more. In addition, from the viewpoint of suppressing excessive water diffusion into the bulk of the A layer, in some embodiments, the amount of the hydrophilic agent used can be, for example, 20 parts by weight or less, suitably 10 parts by weight or less, preferably 5 parts by weight or less, and may be 3 parts by weight or less, per 100 parts by weight of the monomer component. It is preferable that the content of the water affinity agent is not too high from the viewpoint of improving the peel strength N1 after immersion in water, reducing the peel strength reduction rate after immersion in water, or improving the transparency of the pressure-sensitive adhesive layer (A layer). For example, in some embodiments, the content of the water affinity agent relative to 100 parts by weight of the monomer component may be less than 2 parts by weight, less than 1 part by weight, less than 0.7 parts by weight, less than 0.3 parts by weight, or less than 0.2 parts by weight. A water affinity agent with an HLB of 10 or more tends to exhibit good water peelability even when used in small amounts.
[0154] (Acrylic Oligomer) The pressure-sensitive adhesive layer (A layer) disclosed herein may contain an acrylic oligomer from the viewpoints of improving cohesive strength, improving adhesion to the base layer, and improving adhesion to the adherend. The pressure-sensitive adhesive layer (A layer) containing an acrylic oligomer may be formed using a pressure-sensitive adhesive composition A containing the acrylic oligomer. As the acrylic oligomer, one having a higher Tg than the Tg of the above-mentioned acrylic polymer (e.g., acrylic polymer) may be preferably used.
[0155] The Tg of the acrylic oligomer is not particularly limited, and may be, for example, about 20°C or more and 300°C or less. The Tg may be, for example, about 30°C or more, about 40°C or more, about 60°C or more, about 80°C or more, or about 100°C or more. When the Tg of the acrylic oligomer is high, the effect of improving the cohesive force generally tends to be high. In addition, from the viewpoint of anchoring to the base layer and impact absorption, the Tg of the acrylic oligomer may be, for example, about 250°C or less, about 200°C or less, about 180°C or less, or about 150°C or less. The Tg of the acrylic oligomer is a value calculated based on the Fox formula, like the Tg of the acrylic polymer described above.
[0156] The Mw of the acrylic oligomer is not particularly limited, and may be, for example, about 1000 or more, suitably about 1500 or more, about 2000 or more, or about 3000 or more. The Mw of the acrylic oligomer may be, for example, less than about 30000, suitably less than about 10000, less than about 7000, or less than about 5000. When the Mw is within the above range, the cohesiveness and adhesiveness improving effect of the pressure-sensitive adhesive layer (A layer) are easily exhibited. The Mw of the acrylic oligomer can be measured by GPC and calculated as a value converted into standard polystyrene. Specifically, for example, it can be measured using HPLC8020 manufactured by Tosoh Corporation, TSKgelGMH-H(20) x 2 columns as a tetrahydrofuran solvent at a flow rate of about 0.5 mL / min.
[0157] As the monomer component constituting the acrylic oligomer, the above-mentioned various (meth)acrylic acids C 1-20 Examples of (meth)acrylate monomers include alkyl esters, the various alicyclic hydrocarbon group-containing (meth)acrylates described above, the various aromatic hydrocarbon group-containing (meth)acrylates described above, and (meth)acrylates obtained from alcohols derived from terpene compounds. These can be used alone or in combination of two or more.
[0158] From the viewpoint of improving adhesiveness, it is preferable that the acrylic oligomer contains, as a monomer unit, an acrylic monomer having a relatively bulky structure, such as an alkyl (meth)acrylate having a branched structure such as isobutyl (meth)acrylate or t-butyl (meth)acrylate, an alicyclic hydrocarbon group-containing (meth)acrylate, or an aromatic hydrocarbon group-containing (meth)acrylate, etc. In addition, when ultraviolet light is used in synthesizing the acrylic oligomer or in preparing the pressure-sensitive adhesive layer (A layer), a monomer having a saturated hydrocarbon group at the ester end is preferable in terms of being less likely to cause polymerization inhibition, and for example, an alkyl (meth)acrylate having a branched structure such as an alkyl group or a saturated alicyclic hydrocarbon group-containing (meth)acrylate can be suitably used.
[0159] The proportion of (meth)acrylate monomers in all monomer components constituting the acrylic oligomer is typically more than 50% by weight, preferably 60% by weight or more, more preferably 70% by weight or more (e.g., 80% by weight or more, or even 90% by weight or more). In some preferred embodiments, the acrylic oligomer has a monomer composition substantially consisting of one or more (meth)acrylate monomers. The monomer components are an alicyclic hydrocarbon group-containing (meth)acrylate and (meth)acrylic acid C. 1-20 When the alkyl ester is included, the weight ratio thereof is not particularly limited. In some embodiments, the alicyclic hydrocarbon group-containing (meth)acrylate / (meth)acrylic acid C 1-20 The weight ratio of the alkyl esters can be, for example, 10 / 90 or more, 20 / 80 or more, or 30 / 70 or more, and can be 90 / 10 or less, 80 / 20 or less, or 70 / 30 or less.
[0160] In addition to the above (meth)acrylate monomer, functional group-containing monomers can be used as monomer components constituting the acrylic oligomer, if necessary. Examples of functional group-containing monomers include monomers having nitrogen atom-containing heterocycles such as N-vinyl-2-pyrrolidone and N-acryloylmorpholine; amino group-containing monomers such as N,N-dimethylaminoethyl (meth)acrylate; amide group-containing monomers such as N,N-diethyl (meth)acrylamide; carboxy group-containing monomers such as AA and MAA; and hydroxyl group-containing monomers such as 2-hydroxyethyl (meth)acrylate. These functional group-containing monomers can be used alone or in combination of two or more. When a functional group-containing monomer is used, the ratio of the functional group-containing monomer to the total monomer components constituting the acrylic oligomer can be, for example, 1% by weight or more, 2% by weight or more, or 3% by weight or more, and can be, for example, 15% by weight or less, 10% by weight or less, or 7% by weight or less. The acrylic oligomer may not use a functional group-containing monomer.
[0161] Suitable acrylic oligomers include, for example, homopolymers of dicyclopentanyl methacrylate (DCPMA), cyclohexyl methacrylate (CHMA), isobornyl methacrylate (IBXMA), isobornyl acrylate (IBXA), dicyclopentanyl acrylate (DCPA), 1-adamantyl methacrylate (ADMA), and 1-adamantyl acrylate (ADA), as well as copolymers of DCPMA and MMA, copolymers of DCPMA and IBXMA, copolymers of ADA and methyl methacrylate (MMA), copolymers of CHMA and isobutyl methacrylate (IBMA), copolymers of CHMA and IBXMA, copolymers of CHMA and acryloylmorpholine (ACMO), copolymers of CHMA and diethylacrylamide (DEAA), and copolymers of CHMA and AA.
[0162] The acrylic oligomer can be formed by polymerizing its constituent monomer components. The polymerization method and polymerization mode are not particularly limited, and various conventionally known polymerization methods (e.g., solution polymerization, emulsion polymerization, bulk polymerization, photopolymerization, radiation polymerization, etc.) can be used in an appropriate mode. The type of polymerization initiator (e.g., azo-based polymerization initiator) that can be used as necessary is generally as exemplified for the synthesis of acrylic polymers, and the amount of polymerization initiator and the amount of chain transfer agent (e.g., mercaptans) that is optionally used are appropriately set based on technical common sense so as to obtain a desired molecular weight, so detailed explanations are omitted.
[0163] When the adhesive layer (layer A) or the adhesive composition A contains an acrylic oligomer, the content thereof can be, for example, 0.01 parts by weight or more relative to 100 parts by weight of the monomer component of the polymer (typically an acrylic polymer) contained in the adhesive layer (A), and from the viewpoint of obtaining a higher effect, it may be 0.05 parts by weight or more, or 0.1 parts by weight or more, or 0.2 parts by weight or more. In addition, from the viewpoint of compatibility with the above-mentioned polymer (typically an acrylic polymer), the content of the acrylic oligomer relative to 100 parts by weight of the above-mentioned monomer component is suitably less than 50 parts by weight, preferably less than 30 parts by weight, more preferably 25 parts by weight or less, and may be, for example, 10 parts by weight or less, 5 parts by weight or less, or 1 part by weight or less.
[0164] (tackifier resin) The pressure-sensitive adhesive layer (A layer) may contain a tackifier resin. Examples of the tackifier resin include rosin-based tackifier resins, petroleum-based tackifier resins including rosin derivative tackifier resins, terpene-based tackifier resins, phenol-based tackifier resins, and ketone-based tackifier resins. These may be used alone or in combination of two or more.
[0165] Examples of the rosin-based tackifying resin include rosins such as gum rosin, wood rosin, and tall oil rosin, as well as stabilized rosins (e.g., stabilized rosins obtained by disproportionating or hydrogenating the above-mentioned rosins), polymerized rosins (e.g., polymers, typically dimers, of the above-mentioned rosins), and modified rosins (e.g., unsaturated acid-modified rosins modified with unsaturated acids such as maleic acid, fumaric acid, and (meth)acrylic acid). Examples of the rosin derivative tackifying resin include esters of the rosin-based tackifying resins (for example, rosin esters such as stabilized rosin ester and polymerized rosin ester), phenol-modified products of the rosin-based resins (phenol-modified rosin) and esters thereof (phenol-modified rosin ester). Examples of the petroleum-based tackifying resin include aliphatic petroleum resins, aromatic petroleum resins, copolymer petroleum resins, alicyclic petroleum resins, and hydrogenated versions of these. Examples of the terpene tackifier resin include α-pinene resin, β-pinene resin, aromatic modified terpene resin, and terpene phenol resin. Examples of the ketone-based tackifying resin include ketone-based resins obtained by condensation of ketones (e.g., aliphatic ketones such as methyl ethyl ketone, methyl isobutyl ketone, and acetophenone; alicyclic ketones such as cyclohexanone and methylcyclohexanone) with formaldehyde; and the like.
[0166] In some embodiments, the tackifier resin may be one or more selected from rosin-based tackifier resins, rosin derivative tackifier resins, and terpene phenol resins. Among these, rosin derivative tackifier resins are preferred, and suitable examples include rosin esters such as stabilized rosin esters and polymerized rosin esters.
[0167] In the water-dispersed PSA composition, it is preferable to use a water-dispersed tackifier resin in the form in which the tackifier resin is dispersed in an aqueous solvent as described above. For example, by mixing an aqueous dispersion of an acrylic polymer with a water-dispersed tackifier resin, a PSA composition containing these components in a desired ratio can be easily prepared. In some embodiments, the water-dispersed tackifier resin can be preferably one that does not substantially contain at least aromatic hydrocarbon solvents from the viewpoint of environmental hygiene. It is more preferable to use a water-dispersed tackifier resin that does not substantially contain aromatic hydrocarbon solvents or other organic solvents.
[0168] Examples of commercially available water-dispersible tackifier resins containing rosin esters include those manufactured by Arakawa Chemical Industries Co., Ltd. under the trade names "Superester E-720", "Superester E-730-55", and "Superester E-865NT", and those manufactured by Harima Chemical Industries Co., Ltd. under the trade names "Hariestar SK-90D", "Hariestar SK-70D", "Hariestar SK-70E", and "Neotoll 115E". Examples of commercially available terpene phenol resins (which may be in the form of water-dispersible terpene phenol resins) include those manufactured by Arakawa Chemical Industries Co., Ltd. under the trade names "Tamanol E-100", "Tamanol E-200", and "Tamanol E-200NT".
[0169] The softening point of the tackifier resin is not particularly limited. In order to suppress the decrease in the cohesive force of the adhesive layer (A layer), a tackifier resin having a softening point of 80° C. or more can be preferably used. The softening point of the tackifier resin may be 90° C. or more, 100° C. or more, 110° C. or more, or 120° C. or more. A tackifier resin having a softening point of 130° C. or more or 140° C. or more may be used. In addition, in order to improve transparency, adhesion to the base layer, adhesion to the adherend, etc., a tackifier resin having a softening point of 200° C. or less or 180° C. or less can be preferably used. The softening point of the tackifier resin referred to here may be a nominal value described in literature, catalogs, etc. In the absence of a nominal value, the softening point of the tackifier resin may be measured based on the softening point test method (ring and ball method) specified in JIS K5902 or JIS K2207.
[0170] From the viewpoint of optimally exerting the effect of use, the amount of the tackifier resin used is suitably 1 part by weight or more relative to 100 parts by weight of the monomer component constituting the polymer contained in the A layer, and may be 5 parts by weight or more, 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more. Moreover, from the viewpoint of achieving a good balance between adhesion and cohesiveness to the base layer or the adherend, the amount of the tackifier resin used relative to 100 parts by weight of the monomer component may be, for example, 70 parts by weight or less, 50 parts by weight or less, or 40 parts by weight or less. Alternatively, the A layer may be substantially free of the tackifier resin.
[0171] (Silane coupling agent) In some embodiments, the pressure-sensitive adhesive layer (layer A) can contain a silane coupling agent. The layer A containing a silane coupling agent can suitably realize a laminate having a low water immersion peel strength loss rate and a high water peel strength loss rate. The silane coupling agent can be used alone or in combination of two or more.
[0172] Examples of the silane coupling agent include silicon compounds having an epoxy structure such as 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; silicon compounds containing amino groups such as 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)3-aminopropyltrimethoxysilane, and N-(2-aminoethyl)3-aminopropylmethyldimethoxysilane; 3-chloropropyltrimethoxysilane; (meth)acrylic group-containing silane coupling agents such as acetoacetyl group-containing trimethoxysilane, 3-acryloxypropyltrimethoxysilane, and 3-methacryloxypropyltriethoxysilane; and isocyanate group-containing silane coupling agents such as 3-isocyanatepropyltriethoxysilane. Among them, preferred examples include 3-glycidoxypropyltrimethoxysilane and acetoacetyl group-containing trimethoxysilane.
[0173] The amount of the silane coupling agent used can be set so as to obtain the desired effect of use, and is not particularly limited. In some embodiments, the amount of the silane coupling agent used may be, for example, 0.001 parts by weight or more relative to 100 parts by weight of the monomer component constituting the polymer contained in the A layer, and from the viewpoint of obtaining a higher effect, it may be 0.005 parts by weight or more, 0.01 parts by weight or more, or 0.015 parts by weight or more. In addition, from the viewpoint of improving adhesion to the base layer, in some embodiments, the amount of the silane coupling agent used may be, for example, 3 parts by weight or less, 1 part by weight or less, or 0.5 parts by weight or less relative to 100 parts by weight of the monomer component constituting the A layer.
[0174] In an embodiment in which the monomer component contains an alkoxysilyl group-containing monomer, the alkoxysilyl group-containing monomer may be used as a part or the whole of the silane coupling agent contained in the layer A.
[0175] The adhesive composition A used to form the A layer may contain an acid or base (such as aqueous ammonia) used for the purpose of adjusting the pH, etc., as necessary. Examples of other optional components that may be contained in the composition include various additives that are common in the field of adhesive compositions, such as viscosity adjusters (e.g., thickeners), leveling agents, plasticizers, fillers, colorants such as pigments and dyes, stabilizers, preservatives, and antioxidants. As for such various additives, those that are conventionally known can be used in the usual manner, and they do not particularly characterize the present invention, so detailed explanations will be omitted.
[0176] (2)B layer The adhesive layer of the laminate disclosed herein may further include a layer B arranged on the back side of the layer A in addition to the layer A constituting at least the surface of the adhesive layer on the substrate layer side. According to the configuration including the layer A and the layer B in this way, for example, the layer A can be given good water peelability, while the layer B can adjust the bulk properties (for example, water resistance, cohesiveness, heat resistance, etc.) of the adhesive layer. Therefore, according to the adhesive layer including the layer A and the layer B, it is easy to obtain a laminate having good water peelability and excellent water resistance reliability. For example, a laminate having a low rate of peel strength reduction after water immersion and a high rate of water peel strength reduction can be suitably realized. Also, for example, an adhesive layer that combines strong adhesion and good water peelability at a high level can be suitably realized.
[0177] The B layer may be disposed in direct contact with the back surface of the A layer, or may be disposed between the A layer and the B layer via another layer. The other layer (hereinafter also referred to as an intermediate layer) is typically a non-adhesive layer, and may be, for example, a resin film, a foam sheet, a woven fabric, paper, a metal foil, or the like that may be used in the above-mentioned base layer. From the viewpoint of the flexibility of the laminate and the ability to follow the surface shape of the adherend, in some embodiments, a pressure-sensitive adhesive layer in which the A layer and the B layer are laminated in direct contact with each other (i.e., without an intermediate layer) may be preferably used.
[0178] The B layer may be an adhesive layer including one or more adhesives selected from various known adhesives such as acrylic adhesives, rubber adhesives, silicone adhesives, polyester adhesives, urethane adhesives, polyether adhesives, polyamide adhesives, and fluorine adhesives. In some embodiments, an acrylic adhesive may be preferably used as a constituent material of the B layer from the viewpoint of transparency, weather resistance, and the like. The acrylic adhesive constituting the B layer may be selected from those exemplified as acrylic adhesives that can be used in the A layer so that desired properties are exhibited in combination with the A layer. The B layer may be a single-layer structure consisting of one layer, or a multilayer structure including two or more layers having different compositions.
[0179] In some embodiments, the monomer component constituting the polymer (e.g., an acrylic polymer) contained in the B layer is C at a ratio of 40% by weight or more of the total monomer component. 1-20 (Meth)acrylic acid alkyl ester may be included. 1-20 The proportion of the (meth)acrylic acid alkyl ester may be, for example, 98% by weight or less, and from the viewpoint of improving the cohesion of layer B, it may be 95% by weight or less, 85% by weight or less, 70% by weight or less, or 60% by weight or less. The monomer components constituting the B layer may contain a copolymerizable monomer together with the (meth)acrylic acid alkyl ester. The copolymerizable monomer may be appropriately selected from those exemplified as the copolymerizable monomers that may be used in the A layer. The amount of the copolymerizable monomer used may be, for example, 5% by weight or more, 15% by weight or more, 30% by weight or more, or 40% by weight or more of the total monomer components constituting the B layer.
[0180] In some embodiments, the proportion of the carboxyl group-containing monomer in the monomer components constituting the B layer may be, for example, 2% by weight or less, 1% by weight or less, or 0.5% by weight or less. The monomer components constituting the B layer may not substantially contain a carboxyl group-containing monomer. Here, "substantially not containing a carboxyl group-containing monomer" means that at least intentionally not containing a carboxyl group-containing monomer. The pressure-sensitive adhesive layer having the B layer with such a composition is preferred because it is likely to have high water resistance and reliability.
[0181] A suitable example of a pressure-sensitive adhesive layer having a layer A and a layer B is a pressure-sensitive adhesive layer that satisfies one or both of the following: the gel fraction of layer B is higher than that of layer A, and the swelling degree of layer B is lower than that of layer A. With such a configuration, a pressure-sensitive adhesive layer that has a low rate of decrease in peel strength after immersion in water and a high rate of decrease in peel strength in water is easily obtained.
[0182] In some embodiments, the B layer may be a layer formed from a photocurable adhesive composition or a solvent-based adhesive composition. The B layer formed from such a composition is likely to provide an adhesive layer with good water resistance reliability. For example, a combination of the A layer formed from a water-dispersible adhesive composition and the B layer formed from a photocurable adhesive composition, or a combination of the A layer formed from a water-dispersible adhesive composition and the B layer formed from a solvent-based adhesive composition, can suitably provide an adhesive layer with a low water immersion peel strength reduction rate and a high water peel strength reduction rate. In some embodiments, from the viewpoint of improving water resistance, the B layer that does not substantially contain a hydrophilic agent can be preferably used.
[0183] (3) Common matters regarding adhesive layer The adhesive layer may be a cured layer of the adhesive composition. That is, the adhesive layer may be formed by applying (for example, coating) the adhesive composition to a suitable surface and then appropriately carrying out a curing treatment. When two or more types of curing treatments (drying, crosslinking, polymerization, etc.) are performed, they may be performed simultaneously or in multiple stages. In the case of an adhesive composition using a partial polymer of a monomer component (acrylic polymer syrup), typically, a final copolymerization reaction is performed as the curing treatment. That is, the partial polymer is subjected to a further copolymerization reaction to form a complete polymer. For example, in the case of a photocurable adhesive composition, light irradiation is performed. If necessary, curing treatments such as crosslinking and drying may be performed. For example, if drying is required for a photocurable adhesive composition, photocuring may be performed after drying. In the case of an adhesive composition using a complete polymer, typically, drying (heat drying), crosslinking, etc. are performed as the curing treatment as necessary. An adhesive layer having a multilayer structure of two or more layers can be prepared by laminating adhesive layers formed in advance. Alternatively, the second pressure-sensitive adhesive layer may be formed by applying a pressure-sensitive adhesive composition onto a first pressure-sensitive adhesive layer that has been formed in advance, and then curing the pressure-sensitive adhesive composition.
[0184] The pressure-sensitive adhesive composition can be applied using a conventional coater such as a gravure roll coater, a reverse roll coater, a kiss roll coater, a dip roll coater, a bar coater, a knife coater, a spray coater, etc. For example, as a method for providing a pressure-sensitive adhesive layer on a substrate layer, a direct method in which a pressure-sensitive adhesive composition is directly applied to the substrate layer to form a pressure-sensitive adhesive layer may be used, or a transfer method in which a pressure-sensitive adhesive layer formed on a release surface is transferred to the substrate layer may be used.
[0185] The thickness of the adhesive layer is not particularly limited, and may be, for example, about 3 μm to 1000 μm. From the viewpoint of increasing the water resistance reliability by adhering the adhesive layer to the base layer or the adherend, in some embodiments, the thickness of the adhesive layer may be, for example, 5 μm or more, 10 μm or more, 20 μm or more, 30 μm or more, 50 μm or more, more than 50 μm, 70 μm or more, 100 μm or more, or 120 μm or more. In addition, from the viewpoint of preventing the occurrence of adhesive residue due to cohesive failure of the adhesive layer, in some embodiments, the thickness of the adhesive layer may be, for example, 500 μm or less, 300 μm or less, 200 μm or less, or 170 μm or less. The technology disclosed herein may also be preferably applied to a laminate in which the thickness of the adhesive layer is 130 μm or less, 90 μm or less, 60 μm or less, or 40 μm or less.
[0186] In some preferred embodiments, the pressure-sensitive adhesive layer is made of layer A. In other words, the pressure-sensitive adhesive layer may have a single-layer structure of layer A only, without layer B. According to the technology disclosed herein, excellent water peelability is realized by forming a hydrophilic layer on the surface of the base layer, so there is no need to make the pressure-sensitive adhesive layer a multilayer structure in order to achieve both water peelability and other properties (for example, water resistance reliability). In other words, the desired properties can be realized without relying on layer B. This is advantageous from the viewpoint of the production efficiency of the pressure-sensitive adhesive layer. In addition, according to a laminate in which the pressure-sensitive adhesive layer is made of layer A, when the adherend has a hydrophilic surface such as a glass material (for example, an alkali glass plate), the laminate can have excellent water peelability not only from the base layer but also from the adherend. In addition, in the pressure-sensitive adhesive layer made of layer A, the thickness of the pressure-sensitive adhesive layer means the thickness of layer A.
[0187] When the pressure-sensitive adhesive layer becomes thick, it generally tends to be difficult to achieve both water peelability and water resistance reliability.From this viewpoint, in an embodiment in which the thickness of the pressure-sensitive adhesive layer is, for example, more than 50 μm, the pressure-sensitive adhesive layer may preferably be configured to include an A layer and a B layer.With such a configuration of the pressure-sensitive adhesive layer, even if the pressure-sensitive adhesive layer becomes thick, it is easy to obtain a pressure-sensitive adhesive layer that achieves both water peelability and water resistance reliability at a high level.
[0188] In an embodiment in which the pressure-sensitive adhesive layer includes an A layer and a B layer, the thickness of the A layer may be, for example, 1 μm or more, 2 μm or more, 4 μm or more, 5 μm or more, 10 μm or more, or 15 μm or more. The thickness of the A layer may be, for example, 50 μm or less, 45 μm or less, 35 μm or less, or 25 μm or less. In particular, in an embodiment in which the A layer is formed from a water-dispersible pressure-sensitive adhesive composition portion or an embodiment in which the A layer includes a hydrophilic agent, it is preferable that the thickness of the A layer is not too large from the viewpoints of improving the water resistance reliability of the pressure-sensitive adhesive layer and improving the transparency of the pressure-sensitive adhesive layer.
[0189] In an embodiment in which the pressure-sensitive adhesive layer includes layer A and layer B, the thickness of layer B may be, for example, 5 μm or more, or 10 μm or more. From the viewpoint of better exerting the effect of providing layer B on the back side of layer A, in some embodiments, the thickness of layer B may be, for example, 20 μm or more, 30 μm or more, 50 μm or more, 70 μm or more, or 100 μm or more.
[0190] In an embodiment in which the pressure-sensitive adhesive layer comprises layer A and layer B, the thickness of layer A in the thickness of the entire pressure-sensitive adhesive layer may be, for example, 90% or less, preferably 70% or less, 50% or less, 30% or less, 20% or less, or 15% or less. From the viewpoint of ease of formation of layer A and water peelability, in some embodiments, the thickness of layer A in the thickness of the entire pressure-sensitive adhesive layer may be, for example, 3% or more, 5% or more, 7% or more, or 10% or more.
[0191] <Removal method> According to this specification, a method for peeling a pressure-sensitive adhesive layer from a base layer of a laminate having a base layer and a pressure-sensitive adhesive layer is provided. This method includes a water peeling step of peeling the pressure-sensitive adhesive layer from the base layer while advancing the intrusion of the aqueous liquid into the interface following the movement of the peel front, in a state where the aqueous liquid is present at the interface between the base layer and the pressure-sensitive adhesive layer at the peel front of the pressure-sensitive adhesive layer from the base layer. The pressure-sensitive adhesive layer also includes an A layer constituting the surface on the base layer side. Furthermore, the surface on the pressure-sensitive adhesive layer side of the base layer is subjected to a hydrophilization treatment. The water peeling step allows the pressure-sensitive adhesive layer to be peeled from the base layer by effectively utilizing the aqueous liquid.
[0192] The hydrophilic treatment applied to the surface of the base layer is not particularly limited, and various surface treatments that can reduce the water contact angle can be adopted. A suitable example is the formation of the above-mentioned hydrophilic layer. The details of the formation of the hydrophilic layer are as described above, so repeated explanations will be omitted. Note that the above-mentioned hydrophilic treatment typically does not include corona treatment or plasma treatment.
[0193] As the aqueous liquid, water or a mixed solvent mainly composed of water may be used, which may contain a small amount of additives as necessary. As the solvent other than water constituting the mixed solvent, lower alcohols (e.g., ethyl alcohol) and lower ketones (e.g., acetone) that can be mixed uniformly with water may be used. As the additive, a known surfactant or the like may be used. From the viewpoint of avoiding contamination of the adherend, in some embodiments, an aqueous liquid that does not substantially contain additives may be preferably used. From the viewpoint of environmental hygiene, it is particularly preferable to use water as the aqueous liquid. The water is not particularly limited, and for example, distilled water, ion-exchanged water, tap water, etc. may be used, taking into consideration the purity required depending on the application and ease of availability.
[0194] In some embodiments, the above peeling method can be preferably carried out in the same manner as, for example, when measuring the water peeling force N2, by supplying an aqueous liquid onto the base layer near the outer edge of the adhesive layer attached to the base layer, and then allowing the aqueous liquid to penetrate into the interface between the adhesive layer and the base layer from the outer edge of the adhesive layer, without supplying new water (i.e., using only the aqueous liquid supplied onto the base layer before the start of peeling). If the water that penetrates into the interface between the adhesive layer and the base layer following the movement of the peel front is exhausted during the water peeling process, additional water may be supplied intermittently or continuously after the start of the water peeling process. For example, in cases where the base layer has water absorption properties, or where the aqueous liquid is likely to remain on the surface of the base layer or the adhesive surface after peeling, an embodiment in which additional water is supplied after the start of the water peeling process can be preferably adopted.
[0195] The amount of the aqueous liquid supplied before the start of peeling is not particularly limited, as long as it is an amount that can introduce the aqueous liquid from outside the adhesion range of the adhesive layer to the interface between the adhesive layer and the base layer. The amount of the aqueous liquid may be, for example, 5 μL or more, suitably 10 μL or more, or 20 μL or more. There is no particular limit to the upper limit of the amount of the aqueous liquid. In some embodiments, from the viewpoint of improving workability, the amount of the aqueous liquid may be, for example, 10 mL or less, 5 mL or less, 1 mL or less, 0.5 mL or less, 0.1 mL or less, or 0.05 mL or less. By reducing the amount of the aqueous liquid, the operation of removing the aqueous liquid by drying, wiping, or the like after peeling of the adhesive layer can be omitted or simplified.
[0196] The operation of injecting an aqueous liquid into the interface between the adhesive layer and the base layer from the outer edge of the adhesive layer at the start of peeling can be carried out, for example, by inserting the tip of a tool such as a cutter knife or a needle into the interface at the outer edge of the adhesive layer, scratching and lifting the outer edge of the adhesive layer with a hook or a claw, or attaching a highly adhesive adhesive tape or a suction cup to the back surface near the outer edge of the laminate to lift the end of the adhesive layer. By forcibly injecting the aqueous liquid into the interface from the outer edge of the adhesive layer in this way, a state in which the aqueous liquid is present at the interface between the base layer and the adhesive layer can be efficiently formed. In addition, it is possible to suitably achieve both good water peelability after the operation of forcibly injecting the aqueous liquid into the interface to trigger peeling, and high water resistance reliability when such an operation is not performed.
[0197] The pressure-sensitive adhesive layer to be peeled off by the above peeling method is preferably, for example, any of the pressure-sensitive adhesive layers disclosed herein. The above peeling method is suitable as a method for peeling a pressure-sensitive adhesive layer from a base layer in any of the laminates disclosed herein.
[0198] The water peeling step according to some embodiments can be preferably carried out in an embodiment in which the peel front is moved at a speed of 10 mm / min or more. Moving the peel front at a speed of 10 mm / min or more corresponds to peeling the pressure-sensitive adhesive layer at a pulling speed of 20 mm / min or more, for example, under the condition of a peel angle of 180 degrees. The speed at which the peel front is moved may be, for example, 50 mm / min or more, 150 mm / min or more, 300 mm / min or more, or 500 mm / min or more. According to the peeling method disclosed herein, the pressure-sensitive adhesive layer is peeled from the base layer while the aqueous liquid is allowed to penetrate into the interface, thereby exhibiting good water peelability even at such a relatively high peeling speed. There is no particular upper limit to the speed at which the peel front is moved. The speed at which the peel front is moved may be, for example, 1000 mm / min or less.
[0199] The peeling method disclosed herein is, for example, a method in which the peeling area of the adhesive layer per 10 μL of aqueous liquid (e.g., water) volume used in the method is, for example, 50 cm2 More than 100cm, preferably 100cm 2 The present invention can be implemented in the above-described manner.
[0200] <Application> The laminate disclosed herein can be easily peeled off from the base layer using an aqueous liquid such as water, and therefore has good reworkability and good water resistance reliability. By utilizing the features of being attached to components constituting various mobile devices (portable devices), automobiles, home appliances, etc., it can be used for applications such as fixing, joining, forming, decorating, protecting, and supporting the components. The material constituting at least the surface of the above-mentioned component can be, for example, glass such as an alkali glass plate or non-alkali glass; metal materials such as resin films, stainless steel (SUS), and aluminum; resin materials such as acrylic resin, ABS resin, polycarbonate resin, polystyrene resin, and transparent polyimide resin; etc. The laminate disclosed herein may be attached to a painted surface with a paint such as an acrylic-based, polyester-based, alkyd-based, melamine-based, urethane-based, acid-epoxy crosslinked, or a composite of these (for example, an acrylic-melamine-based, alkyd-melamine-based) paint, or a plated surface such as a zinc-plated steel sheet.
[0201] The water contact angle of the surface of the adherend to which the laminate is attached is not particularly limited. In some embodiments, the adherend surface may be a surface that exhibits hydrophilicity such that the water contact angle is, for example, 60 degrees or less, preferably 50 degrees or less. In some preferred embodiments, the water contact angle of the surface may be, for example, 45 degrees or less, 40 degrees or less, 35 degrees or less, or 30 degrees or less. When the water contact angle is small, water tends to spread easily along the adherend surface, and the water peelability of the laminate tends to improve. The laminate disclosed herein can be preferably used, for example, for fixing a member having a surface made of a material (e.g., glass such as an alkali glass plate or non-alkali glass) having a water contact angle of about 30 degrees or less (e.g., 15 degrees or less, or even 10 degrees or less). The lower limit of the water contact angle of the adherend surface is 0 degrees in principle. In some embodiments, the water contact angle of the adherend surface may be more than 0 degrees, 1 degree or more, 3 degrees or more, or 5 degrees or more. In some other embodiments, the water contact angle of the adherend surface may be more than 30 degrees, more than 50 degrees, or more than 60 degrees (e.g., 70 degrees or more). The laminate disclosed herein can be used for various materials with different water contact angles. The water contact angle of the adherend surface is measured by a method similar to that described in the examples below.
[0202] The laminate disclosed herein is preferably used in, for example, display devices (image display devices) such as liquid crystal display devices, organic EL (electroluminescence) display devices, PDPs (plasma display panels), and electronic paper, and devices (optical devices) such as input devices such as touch panels, particularly when expensive components are included, such as foldable display devices and in-vehicle display devices.
[0203] The embodiment of bonding an optical member using the laminate disclosed herein is not particularly limited, and may be, for example, (1) an embodiment in which the base layer of the laminate disclosed herein is an optical member, and optical members (therefore, the adherend is an optical member) are bonded to each other via a pressure-sensitive adhesive layer, (2) an embodiment in which the base layer of the laminate disclosed herein is an optical member, and the optical member is bonded to a member (adherend) other than an optical member via a pressure-sensitive adhesive layer, or (3) an embodiment in which the base layer of the laminate disclosed herein is a material other than an optical member, and the laminate (specifically, its pressure-sensitive adhesive layer) is bonded to an optical member (adherend). Note that a laminate in which the base layer includes an optical member may also be understood as a pressure-sensitive adhesive optical member (for example, a pressure-sensitive adhesive optical film). In addition, when the base layer of the laminate disclosed herein includes the above-mentioned functional film, the laminate disclosed herein may also be understood as an "adhesive functional film" having the pressure-sensitive adhesive layer disclosed herein on at least one side of the functional film. EXAMPLES
[0204] Some examples of the present invention will be described below, but it is not intended that the present invention be limited to those shown in these examples. In the following description, "parts" and "%" are by weight unless otherwise specified.
[0205] <Evaluation method> [Peel strength N0] A laminate having a width of 20 mm and a length of 100 mm is prepared as a test piece. The adhesive surface of this laminate is backed with a PET film. After the above test piece is autoclaved (50°C, 0.5 MPa, 15 minutes), a cutter knife is inserted into the interface between the base layer and the adhesive layer in an environment of 23°C and 50% RH, and one end of the adhesive layer in the longitudinal direction is peeled off from the base layer. Using a tensile tester (Minebea Co., Ltd., universal tensile compression tester, device name "tensile compression tester, TCM-1kNB"), the peel strength of the adhesive layer from the base layer is measured at a tensile speed of 300 mm / min and a peel angle of 180 degrees (however, the peel strength is measured until the water peel force measurement described below is started, that is, until distilled water is supplied to the peel interface). The measurement is performed three times, and the average value converted into a value per 10 mm width (unit: N / 10 mm) is taken as the peel strength N0 [N / 10 mm]. The peel strength is measured so that the peel of the test piece attached to the adherend proceeds from bottom to top. As the tensile tester, an equivalent of the universal tensile compression tester described above may be used. For laminates including a photocurable adhesive layer, the test pieces removed from the autoclave are irradiated with light through the base layer in an environment of 23°C and 50% RH, and then the peel strength is measured. The light irradiation conditions (wavelength, irradiation intensity, irradiation time, etc.) are appropriately set depending on the composition, thickness, etc. of the adhesive layer. Specifically, for the laminates of Examples 1-1 to 1-30 described below, after the autoclave treatment, the laminates are irradiated with light from a high-pressure mercury lamp (300 mW / cm 2 ) from the substrate layer side with an integrated light quantity of 3000 mJ / cm 2 The photocurable pressure-sensitive adhesive layer is cured by irradiating it with ultraviolet light. In Examples 2-1 to 2-24, light irradiation after the autoclave treatment is not carried out. When a non-adhesive layer is disposed on the back side of the adhesive layer, the backing with a PET film is not necessary.
[0206] [Water peeling force N2] In the measurement of the peel strength N0, 20 μL of distilled water is supplied to the location (peel interface) where the adhesive layer starts to separate from the base layer during the measurement of the peel strength N0 from the base layer, and the peel strength after the distilled water supply is measured. The measurement is performed for each peel strength measurement (i.e., three times), and the average value is converted to a value per 10 mm width (unit: N / 10 mm) to obtain the water peel strength N2 [N / 10 mm]. The conditions for measuring the peel strength after supplying distilled water shall be in accordance with JIS Z0237:2009, 10.4.1, Method 1: 180° peel adhesion to test plate. Specifically, the test temperature shall be 23°C, a tensile tester shall be used, the tensile speed shall be 300mm / min, and the peel angle shall be 180°. In this embodiment, the peel strength and the water peel strength are measured continuously for each test piece, but the peel strength and the water peel strength may be measured using different test pieces. For example, when it is difficult to prepare a test piece of sufficient length to perform continuous measurement, a mode of performing measurements using different test pieces can be adopted. In this case, a cutter knife is inserted into the interface between the base layer and the pressure-sensitive adhesive layer to peel off one end of the pressure-sensitive adhesive layer in the longitudinal direction from the base layer, and distilled water is supplied thereto to perform the peel strength measurement.
[0207] [Peel strength after water immersion N1] The laminate is cut into a rectangular shape with a width of 10 mm and a length of 120 mm to prepare a test piece. This test piece is placed in an autoclave and treated for 15 minutes under conditions of a pressure of 5 atm and a temperature of 50°C. The evaluation sample removed from the autoclave is kept in an environment of 23°C and 50% RH for one day, and then immersed in water at room temperature (23°C to 25°C) for 30 minutes. Ion-exchanged water or distilled water is used as the water. The test piece is held horizontally in the water with the adhesive layer facing up. The distance from the top surface of the test piece to the water surface (immersion depth) is 10 mm or more (for example, about 10 mm to 100 mm). Next, the test piece is taken out of the water, the water adhering to the test piece is gently wiped off, and then a cutter knife is inserted into the interface between the adhesive layer and the base layer to peel off one end of the adhesive layer in the longitudinal direction, and the peel strength of the adhesive layer from the base layer is measured in an environment of 23°C and 50% RH according to "10.4.1 Method 1: 180° peel adhesion to test plate" of JIS Z0237:2009, specifically, at a test temperature of 23°C, a tensile tester at a tensile speed of 300 mm / min, and a peel angle of 180°. The measured value is the peel strength after water immersion N1 [N / 10 mm]. The time from taking the test piece out of the water to measuring the peel strength is within 10 minutes.
[0208] The measurement conditions for the peel strength after water immersion are the same as those for the peel strength N0, except for the water immersion. Specifically, in the measurement of the peel strength N1 after water immersion, for a laminate including a photocurable adhesive layer, the sample taken out of the autoclave is irradiated with light through the base layer in an environment of 23°C and 50% RH, and then immersed in water to measure the peel strength. The light irradiation conditions (wavelength, irradiation intensity, irradiation time, etc.) may be appropriately set according to the composition and thickness of the adhesive layer. In addition, as the tensile tester, a universal tensile compression tester (apparatus name "Tension and compression tester, TCM-1kNB" manufactured by Minebea Co., Ltd.) or an equivalent can be used. The peel strength is measured so that the peel of the test piece attached to the adherend proceeds from bottom to top. In the measurement, if necessary, a suitable backing material can be attached to the back surface of the laminate (the surface opposite to the surface of layer A) to reinforce the test piece. As the backing material, for example, a PET film having a thickness of about 25 μm can be used.
[0209] [Film thickness measurement] The silicon oxide film thickness is calculated by measuring the X-ray reflectance using a powder X-ray diffraction device (Rigaku Corporation, device name "RINT-2000") under the following measurement conditions, and analyzing the obtained measurement data using analysis software (Rigaku Corporation, "GXRR3"). The analysis conditions are as follows: polymer film substrate, density 2.3 g / cm 3 A two-layer model of the silicon oxide film is adopted, and the thickness of the silicon oxide layer is analyzed by performing least squares fitting using the film thickness and surface roughness of the silicon oxide film and the surface roughness of the substrate film as variables. (Measurement conditions) Light source: Cu-Kα line (wavelength: 1.5418Å), 40kV, 40mA Optical system: Parallel beam optical system Divergence slit: 0.05mm Receiving slit: 0.05mm Monochromatization and collimation: Using multi-layer Goebel mirrors Measurement mode: θ / 2θ scan mode Measurement range (2θ): 0.3~1.5° (Analysis conditions) Analysis method: Least squares fitting Analysis range (2θ): 2θ=0.3~1.5°
[0210] [Water contact angle measurement] The water contact angle of the hydrophilic layer surface of the base layer material is measured as follows. That is, in a measurement atmosphere of 23°C and 50% RH, the measurement is performed by the sessile drop method using a contact angle meter (manufactured by Kyowa Interface Science Co., Ltd., product name "DMo-501 type", control box "DMC-2", control and analysis software "FAMAS (version 5.0.30)"). The amount of distilled water dropped is 2 μL, and the contact angle is calculated by the Θ / 2 method from the image 5 seconds after the drop (performed with N5).
[0211] [Water peelability] Peel strength N0 [N / 10mm] and water peel force N2 [N / 10mm] are calculated using the formula: Water peeling force reduction rate [%] = (1-(N2 / N0)) × 100; and a water peel strength reduction rate of 40% or more is evaluated as "◯", and a water peel strength reduction rate of less than 40% is evaluated as "×".
[0212] <Preparation of substrate layer material> (Preparation examples A1 to A5) A silicon oxide film was formed on a PET film substrate A (PET-A; manufactured by Mitsubishi Chemical Corporation, product name "LC-N50JBN", thickness 50 μm) using RF (Radio-Frequency) magnetron sputtering from a Si metal target manufactured by Mitsui Kinzoku Co., Ltd. Argon and oxygen were used as sputtering gases, and the oxygen / argon ratio was 5.3 vol%. By adjusting the film formation time under the above conditions, silicon oxide films with different film thicknesses were formed, and substrate layer materials A1 to A5 corresponding to Preparation Examples A1 to A5, respectively, were obtained.
[0213] (Preparation examples A6-A8) A silicon oxide film was formed on a PET film in the same manner as in Preparation Examples A3 to A5, except that a PET film substrate B (PET-B; manufactured by Mitsubishi Chemical Corporation, product name "Diafoil O300E", thickness 125 μm) was used as the substrate. By adjusting the deposition time under the above conditions, silicon oxide films with different thicknesses were formed, and substrate layer materials A6 to A8 corresponding to Preparation Examples A6 to A8, respectively, were obtained.
[0214] (Preparation examples A9 to A11) A silicon oxide film was formed on the surface of PET film substrate B (PET-B; Mitsubishi Chemical Corporation, product name "Diafoil O300E", thickness 125 μm) using an ALD (atomic layer deposition) device (Picosun, device name "R200"). Bis(diethylamino)silane (Japan Air Liquide, product name "SAM24") was used as the precursor of silicon oxide. The specific reaction steps were as follows: first, the vaporized precursor was introduced into the chamber, followed by evacuation and nitrogen gas purging. Next, oxygen plasma was introduced, followed by evacuation and nitrogen gas purging. The above reaction steps were repeated and the number of steps was adjusted to form silicon oxide films of different thicknesses on the surface of the above substrate, and substrate layer materials A9 to A11 corresponding to Preparation Examples A9 to A11, respectively, were obtained.
[0215] (Preparation examples A12 to A14) A silicon oxide film was formed on a triacetyl cellulose (TAC) film (manufactured by Fuji Film Corporation, product name "TD80UL", thickness 80 μm, refractive index 1.49) in the same manner as in Preparation Examples A9 to A11, except that a silicon oxide film was formed on the TAC film as the substrate. By adjusting the number of reaction steps, silicon oxide films with different thicknesses were formed on the surface of the substrate, and substrate layer materials A12 to A14 corresponding to Preparation Examples A12 to A14, respectively, were obtained.
[0216] (Preparation Example A15) A hydrophilic coating agent was applied to the surface of a TAC film (manufactured by Fuji Film Corporation, product name "TD80UL", thickness 80 μm, refractive index 1.49) as a substrate using a wire bar #5 (manufactured by RDS Corporation), and then dried at 120°C for 2 minutes to form a hydrophilic coating layer with a thickness of 0.2 μm to 0.5 μm. The hydrophilic coating agent used was "Colcoat N-103X" manufactured by Colcoat Corporation. In this way, a TAC film A15 having a hydrophilic coating layer (polysiloxane-based coating layer) was obtained.
[0217] (Preparation examples A16-A18) A silicon oxide film was formed on a transparent polyimide (CPI) film (manufactured by KOLON INDUSTIES INC., product name "C_80", thickness 80 μm) in the same manner as in Preparation Examples A9 to A10, except that the substrate was a CPI film. By adjusting the number of reaction steps, silicon oxide films of different thicknesses were formed on the surface of the substrate, and substrate layer materials A16 to A18 corresponding to Preparation Examples A16 to A18, respectively, were obtained.
[0218] (Preparation examples A19-A21) A silicon oxide film was formed on a polarizing plate in the same manner as in Preparation Examples A16 to A18, except that a polarizing plate (manufactured by Nitto Denko Corporation, product name "REGQ-HC3", thickness 92 μm) was used as the substrate. By adjusting the number of reaction steps, silicon oxide films with different thicknesses were formed on the surface of the substrate, and substrate layer materials A19 to A21 corresponding to Preparation Examples A19 to A21, respectively, were obtained.
[0219] <Preparation of adhesive> (Preparation example B1) In a reaction vessel equipped with a cooling tube, a nitrogen inlet tube, a thermometer and a stirrer, 64.5 parts of n-butyl acrylate (BA), 6 parts of cyclohexyl acrylate (CHA), 15 parts of N-vinyl-2-pyrrolidone (NVP), 5 parts of isostearyl acrylate (iSTA) and 14.9 parts of 4-hydroxybutyl acrylate (4HBA) were charged as monomer components, 0.07 parts of α-thioglycerol as a chain transfer agent, and 122 parts of ethyl acetate as a polymerization solvent. 0.2 parts of 2,2'-azobisisobutyronitrile (AIBN) were added as a thermal polymerization initiator, and solution polymerization was carried out under a nitrogen atmosphere to obtain a solution containing an acrylic polymer with Mw of 600,000.
[0220] The solution obtained above was mixed with 1.0 part of dipentaerythritol hexaacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name "A-DPH") and 3.0 parts of polypropylene glycol #400 diacrylate (manufactured by Shin-Nakamura Chemical Co., Ltd., product name "APG-400") as photoreactive compounds, 1-hydroxycyclohexyl-phenyl-ketone (IGM) as a photoreaction catalyst (photoreaction initiator) and 1.0 parts of 1-hydroxycyclohexyl-phenyl-ketone (IGM) as a photoreaction catalyst (photoreaction initiator) per 100 parts of the monomer components used in the preparation of the solution. 0.22 parts of Regins (trade name: Omnirad 184), 0.16 parts of an isocyanate-based crosslinking agent (trimethylolpropane / xylylene diisocyanate adduct (Mitsui Chemicals, Inc., trade name: Takenate D-110N, solid content concentration 75%) on a solid basis, 0.011 parts of dioctyltin dilaurate (Tokyo Fine Chemicals, Inc., trade name: Envirizer OL-1) as a crosslinking accelerator, 3.33 parts of acetylacetone as a crosslinking retarder, 0.4 parts of an acrylic oligomer, and 0.3 parts of a nonionic surfactant A (polyoxyethylene sorbitan monolaurate, HLB 13.3, trade name: Rheodol TW-L106, Kao Corporation) as a hydrophilic agent were added and mixed uniformly to prepare a solvent-based pressure-sensitive adhesive composition B1 according to this preparation example.
[0221] The acrylic oligomer used was synthesized by the following method. [Synthesis of acrylic oligomers] 100 parts of toluene, 60 parts of dicyclopentanyl methacrylate (DCPMA) (trade name: FA-513M, Hitachi Chemical Co., Ltd.), 40 parts of methyl methacrylate (MMA), and 3.5 parts of α-thioglycerol as a chain transfer agent were charged into a four-neck flask. Then, after stirring at 70°C under a nitrogen atmosphere for 1 hour, 0.2 parts of AIBN were charged as a thermal polymerization initiator, and the mixture was reacted at 70°C for 2 hours, and then at 80°C for 2 hours. Thereafter, the reaction liquid was charged under a temperature atmosphere of 130°C, and the toluene, chain transfer agent, and unreacted monomers were dried and removed to obtain a solid acrylic oligomer. The Tg of this acrylic oligomer was 144°C, and the Mw was 4300.
[0222] A 38 μm-thick release film (Mitsubishi Plastics, Inc., MRF#38) with one side of a polyester film being the release surface, and a 38 μm-thick release film (Mitsubishi Plastics, Inc., MRE#38) with one side of a polyester film being the release surface were prepared. The solvent-based adhesive composition B1 prepared above was applied to the release surface of one of the release films (MRF#38), and dried at 60°C for 3 minutes and then at 120°C for 3 minutes to form a photocurable adhesive layer with a thickness of 150 μm. The release surface of the other release film (MRE#38) was attached to this adhesive layer for protection. In this way, an adhesive layer B1 with the surface protected by two release films was obtained.
[0223] (Preparation example B2) An aqueous emulsion of a monomer mixture (monomer emulsion) was prepared by mixing and emulsifying 85 parts of 2-ethylhexyl acrylate (2EHA), 13 parts of methyl acrylate (MA), 1.2 parts of acrylic acid (AA), 0.8 parts of methacrylic acid (MAA), 0.02 parts of 3-methacryloxypropyltrimethoxysilane (KBM-503, manufactured by Shin-Etsu Chemical Co., Ltd.), 0.048 parts of t-dodecyl mercaptan as a chain transfer agent, and 2.0 parts of an emulsifier (LATEMUL E-118B, manufactured by Kao Corporation) in 100 parts of ion-exchanged water. The monomer emulsion was placed in a reaction vessel equipped with a cooling tube, a nitrogen introduction tube, a thermometer, and a stirrer, and stirred at room temperature for 1 hour or more while introducing nitrogen gas. The system was then heated to 60°C, and 0.1 parts of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]hydrate (VA-057, manufactured by Wako Pure Chemical Industries, Ltd.) was added as a polymerization initiator, and reacted at 60°C for 6 hours to obtain an aqueous dispersion of an acrylic polymer. After cooling the system to room temperature, 30 parts of a tackifier resin emulsion (Superester E-865NT, manufactured by Arakawa Chemical Industries, Ltd., an aqueous dispersion of polymerized rosin ester with a softening point of 160°C) was added in solids per 100 parts of the aqueous dispersion of the acrylic polymer. Furthermore, the pH was adjusted to approximately 7.5 and the viscosity to approximately 9 Pa s using 10% aqueous ammonia as a pH adjuster and polyacrylic acid (aqueous solution with 36% non-volatile content) as a thickener, thereby preparing emulsion-type pressure-sensitive adhesive composition B2 according to this preparation example.
[0224] A 38 μm-thick release film (Mitsubishi Plastics, Inc., MRF#38) with one side of a polyester film being the release surface, and a 38 μm-thick release film (Mitsubishi Plastics, Inc., MRE#38) with one side of a polyester film being the release surface were prepared. The adhesive composition B2 was applied to the release surface of one of the release films (MRF#38) and dried at 120° C. for 3 minutes to form an adhesive layer B2 with a thickness of 20 μm. The release surface of the other release film (MRE#38) was attached to this adhesive layer for protection. In this way, an adhesive layer B2 with a surface protected by two release films was obtained.
[0225] <Example 1-1 to Example 1-21> The release liner covering one surface of the photocurable adhesive layer B1 obtained above was peeled off, and a 25 μm thick PET film was attached to the exposed adhesive surface to provide a backing. This was cut to a size of 20 mm wide and 100 mm long, and then, under an environment of 23° C. and 50% RH, the release liner covering the other surface of the photocurable adhesive layer B1 was peeled off, and the exposed adhesive surface was pressed against the hydrophilic layer-forming surface of each of the base layer materials A1 to A21 by rolling a 2 kg rubber roller back and forth once to laminate the photocurable adhesive layer and the base layer, thereby obtaining laminates according to Examples 1-1 to 1-21. A PET film (backing film) was laminated on the adhesive surface (opposite the surface on the base layer side) of each laminate in each example.
[0226] <Example 1-22 to Example 1-26> Corona treatment was performed on one surface of each of the following: PET film substrate A (PET-A; manufactured by Mitsubishi Chemical Corporation, trade name "LC-N50JBN", thickness 50 μm), PET film substrate B (PET-B; manufactured by Mitsubishi Chemical Corporation, trade name "Diafoil O300E", thickness 125 μm), TAC film (manufactured by Fujifilm Corporation, trade name "TD80UL", thickness 80 μm, refractive index 1.49), CPI film (manufactured by KOLON INDUSTIES INC., trade name "C_80", thickness 80 μm), and polarizing plate (manufactured by Nitto Denko Corporation, trade name "REGQ-HC3", thickness 92 μm). Specifically, the corona treatment was performed by passing the above substrate layer material through a table-type surface corona treatment device (manufactured by KASUGA Corporation, device name "AGF-012") once under the conditions of output setting 3 (display 0.17 kW) and table speed scale 20 (corresponding to a speed of 3 m / min). In addition, the release liner covering one surface of the photocurable adhesive layer B1 obtained above was peeled off, and a 25 μm thick PET film was attached to the exposed adhesive surface to provide a backing. This was cut to a size of 20 mm wide and 100 mm long. Next, immediately after the corona treatment (within 30 minutes after the corona treatment), in an environment of 23° C. and 50% RH, the release liner covering the other surface of the photocurable adhesive layer B1 was peeled off, and the exposed adhesive surface was pressed against the corona-treated surface of the base layer material by rolling a 2 kg rubber roller back and forth once, thereby laminating the photocurable adhesive layer and the base layer, thereby obtaining laminates according to Examples 1-22 to 1-26. A PET film (backing film) was laminated on the adhesive surface (the surface opposite to the base layer surface) of the laminate of each example.
[0227] <Example 1-27~Example 1-30> The release liner covering one surface of the photocurable adhesive layer B1 obtained above was peeled off, and a PET film having a thickness of 25 μm was attached to the exposed adhesive surface as a backing. This was cut to a size of 20 mm in width and 100 mm in length, and then, in an environment of 23°C and 50% RH, the release liner covering the other surface of the photocurable adhesive layer B1 was peeled off, and the exposed adhesive surface was pressed against one surface of each of a PET film substrate A (PET-A; manufactured by Mitsubishi Chemical Corporation, product name "LC-N50JBN", thickness 50 μm), a PET film substrate B (PET-B; manufactured by Mitsubishi Chemical Corporation, product name "Diafoil O300E", thickness 125 μm), a CPI film (manufactured by KOLON INDUSTIES INC., product name "C_80", thickness 80 μm), and a polarizing plate (manufactured by Nitto Denko Corporation, product name "REGQ-HC3", thickness 92 μm) by rolling a 2 kg rubber roller back and forth once, thereby laminating the photocurable adhesive layer and the substrate layer, and obtaining laminates according to Examples 1-27 to 1-30. A PET film (backing film) was laminated on the adhesive surface (the surface opposite to the substrate layer surface) of the laminate in each example.
[0228] <Example 2-1 to Example 2-24> Laminates according to each example were obtained in the same manner as in Examples 1-1 to 1-21, 1-27 to 1-28, and 1-30, except that, as the adhesive layer, adhesive layer B2 was used instead of photocurable adhesive layer B1.
[0229] <Performance evaluation> For each laminate, peel strength N0 [N / 10 mm] and water peeling force N2 [N / 10 mm] were measured, and water peelability was evaluated. The results are shown in Tables 1 and 2. Each table also shows an overview of each example, the film thickness [nm] of the hydrophilic layer in the base layer, and the water contact angle [°] of the adhesive layer side surface of the base layer before lamination of the adhesive layer. In addition, peel strength N1 [N / 10 mm] after water immersion was measured for each laminate.
[0230] [Table 1]
[0231] [Table 2]
[0232] As shown in Tables 1 and 2, in the laminates according to Examples 1-1 to 1-21 in which a hydrophilic layer was provided on the surface of the base layer, the pressure-sensitive adhesive layer and the base layer were bonded with sufficient peel strength in all the examined base materials, and the water releasability was also excellent. In contrast, the laminates according to Examples 1-22 to 1-26 in which the surface of the base layer was subjected to a corona treatment could not obtain good water releasability. The same was true for Examples 1-27 to 1-30 in which the corona treatment was not performed. In addition, in Examples 2-1 to 2-24 in which an emulsion-type pressure-sensitive adhesive was used, the laminates of Examples 2-1 to 2-21 in which a hydrophilic layer was provided on the surface of the base layer had excellent water releasability compared to Examples 2-22 to 2-24 in which no hydrophilic layer was provided. In addition, in the above Examples 2-1 to 2-21, the pressure-sensitive adhesive layer and the base layer were bonded with sufficient peel strength.
[0233] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes of the specific examples exemplified above. [Explanation of symbols]
[0234] 1,2 Laminate 10 Adhesive layer (A layer) 10A One surface (surface on the substrate layer side) 10B Other surface (adhesive side) 20 Base material layer 20A Rear 20B Adhesive layer side surface 22 Main layer 24 Hydrophilic layer 30 Release Liner 50 Laminate with release liner 110 Adhesive layer 110A One surface (substrate layer side surface) 110B Other surface (adhesive surface) 112 A layer 114 B layer
Claims
1. A laminate having a base layer and a pressure-sensitive adhesive layer releasably laminated on the base layer, the base layer is an optical member, or the pressure-sensitive adhesive layer is used by being attached to an optical member as an adherend, The pressure-sensitive adhesive layer includes a layer A constituting a surface on the side of the base layer, The layer A contains an acrylic polymer and a water compatibility agent, The hydrophilic agent is at least one compound selected from a surfactant and a compound having a polyoxyalkylene skeleton, a hydrophilic layer is formed on a surface of the base layer facing the pressure-sensitive adhesive layer, the hydrophilic layer having a surface with a water contact angle of 60 degrees or less; the hydrophilic layer is an inorganic oxide-containing layer, The peel strength N0 of the pressure-sensitive adhesive layer to the base layer is 2.0 N / 10 mm or more, and A laminate in which 20 μL of distilled water is supplied between the base layer and the pressure-sensitive adhesive layer, the distilled water is allowed to penetrate into one end of the interface between the pressure-sensitive adhesive layer and the base layer, and then a water peel strength reduction rate calculated from the water peel strength N2 [N / 10 mm] measured in accordance with JIS Z0237:2009, Section 10.4.1, Method 1: 180° peel adhesion to test plate, specifically, at a test temperature of 23° C. using a tensile tester at a tensile speed of 300 mm / min and a peel angle of 180°, and the peel strength N0 [N / 10 mm] using the following formula: (1-(N2 / N0))×100; is 40% or more.
2. The laminate according to claim 1 , wherein the peel strength N0 is 3.0 N / 10 mm or more.
3. 3. The laminate according to claim 1, wherein a peel strength reduction rate after water immersion is 30% or less, the peel strength reduction rate being calculated from a peel strength N1 [N / 10 mm] after water immersion measured after the laminate is immersed in water for 30 minutes, then removed from the water and wiped off, and the peel strength N0 [N / 10 mm] according to the following formula: (1-(N1 / N0)) x 100.
4. The laminate according to any one of claims 1 to 3, wherein the layer A is a layer formed from a photocurable or solvent-based pressure-sensitive adhesive composition.
5. The laminate according to any one of claims 1 to 4, wherein the inorganic oxide is silicon oxide.
6. The laminate according to any one of claims 1 to 5, wherein the hydrophilic layer has a thickness of less than 5000 nm.
7. The laminate according to any one of claims 1 to 6, wherein the base layer is an optical member.
8. A method for peeling a pressure-sensitive adhesive layer from a substrate layer of a laminate having a substrate layer and a pressure-sensitive adhesive layer, comprising the steps of: a water peeling step of peeling the PSA layer from the base layer while advancing the aqueous liquid into the interface in accordance with the movement of the peel front, in a state in which the aqueous liquid is present at the interface between the base layer and the PSA layer at the peel front of the PSA layer from the base layer, The pressure-sensitive adhesive layer includes a layer A constituting a surface on the side of the base layer, The layer A contains an acrylic polymer and a water compatibility agent, The hydrophilic agent is at least one compound selected from a surfactant and a compound having a polyoxyalkylene skeleton, a hydrophilic layer is formed on a surface of the base layer facing the pressure-sensitive adhesive layer, the hydrophilic layer having a surface with a water contact angle of 60 degrees or less; The method for stripping, wherein the hydrophilic layer is an inorganic oxide-containing layer.
Citation Information
Patent Citations
Inorganic thin film laminate and inorganic thin film form
JP2001064608A
Peeling method for adhesive type optical film
JP2005148638A
Water-releasable coated paper and method for producing the same
JP2006299498A
Pressure-sensitive adhesive film
JP2008023926A
Barrier film with carrier sheet and method for manufacturing barrier film with carrier sheet
JP2009226621A